Resist underlayer film-forming composition, resist underlayer film, method for producing resist underlayer film, pattern forming method, and method for manufacturing semiconductor device
By using the underlying film material prepared by specific polyacetylacetone compounds during nanoimprinting, the problem of difficult to take into account both the treatment resistance and high gas permeability is solved, and the high gas permeability, good embedding and flatness of the low-density film is achieved.
Patent Information
- Application Number
- JP2024159863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2024-09-17
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to achieve both treatment resistance and high gas permeability during nanoimprinting, and bubble problems are prone to occur and poor shape.
The underlying film material containing a specific polyacetylacetone compound is used, which inhibits the sealing packaging and cross-linking reaction of the aromatic ring through the polyacetylacetone compound containing an aromatic ring and a specific linking group, thereby forming a low-density film with good gas permeability.
It achieves resistance to treatment, good embedding and smoothness, and has high gas permeability, reducing bubble problems and improving the accuracy of nanoimprinting.
Smart Images

Figure 2025070979000001 
Figure 2025070979000002 
Figure 2025070979000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for forming a resist underlayer film, a resist underlayer film, a method for producing a resist underlayer film, a pattern forming method, and a method for producing a semiconductor device. In particular, the present invention relates to a composition for forming a resist underlayer film for nanoimprinting that can be used for fine patterning by a photo-nanoimprinting method in the process of producing a semiconductor device. [Background technology]
[0002] In the manufacture of semiconductor devices and MEMS, which require miniaturization, photo-nanoimprinting technology, which can form fine structures on the order of several nanometers on a substrate, has been attracting attention. In a typical photo-nanoimprinting technology, a liquid resist composition is first dropped onto a pattern formation area on a substrate using an inkjet method or the like, and the droplets of the resist composition are spread on the substrate (press-spreading). Next, this resist composition is molded using a mold that is transparent to the irradiated light and on which a pattern has been formed. At this time, the droplets of the resist composition spread over the entire gap between the substrate and the mold by capillary action (spreading). The resist composition also fills the inside of the recess on the mold by capillary action (filling). The time until the spreading and filling are completed is the filling time. After the filling of the resist composition is completed, the resist composition is hardened by irradiating light, and then the two are separated. By carrying out these steps, a resist pattern having a predetermined shape is formed on the substrate.
[0003] In the demolding process of the photo-nanoimprint technique, the adhesion between the resist composition and the substrate is important. If the adhesion between the resist composition and the substrate is low, when the mold is detached in the demolding process, a part of the photocured product obtained by curing the resist composition may peel off while still adhering to the mold, resulting in a pattern peeling defect. In this context, a technique for forming an adhesion layer between the resist composition and the substrate, which is a layer for adhering the resist composition to the substrate, has been proposed as a technique for improving the adhesion between the resist composition and the substrate (Patent Document 1).
[0004] Patent Document 2 discloses a reversal process in nanoimprinting, and since Spin On Carbon (SOC) is used as the processed layer, properties such as processing resistance, embeddability, and flatness are required. In addition, the nanoimprinting process on SOC generally involves applying an adhesive layer material for nanoimprinting onto the SOC and then performing imprinting on the SOC. In addition, bubbles generated when a mold is pressed against a curable composition (resist) can cause molding defects, so it is necessary to eliminate the bubbles. Patent Document 3 improves the oxygen permeability of the mold side, but further improvement in defoaming is expected with miniaturization. In light of this background, it has been proposed to eliminate gas from the underlayer film side, and there is a demand for the development of an underlayer film with high gas permeability (Non-Patent Document 1).
[0005] Gas permeability tends to increase with a hydrophobic film for hydrophobic gases and with a hydrophilic film for highly hydrophilic gases. Since relatively hydrophobic gases such as He, H2, N2, and air are selected as the atmosphere for the process of pressing the mold, Patent Document 4 and Patent Document 5 propose a highly hydrophobic film with a high water contact angle as the underlayer film material. However, these documents do not discuss the actual gas permeability. Furthermore, in reality, a relatively hydrophilic gas such as CO2 may be selected. On the other hand, it is known that gas permeability is greatly affected not only by hydrophilicity but also by film density and compounding agents. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2013-202982 [Patent Document 2] Special Publication No. 2006-524919 [Patent Document 3] Patent No. 6703253 specification [Patent Document 4] International Publication No. 2021-125036 [Patent Document 5] International Publication No. 2023-145923 [Non-patent literature]
[0007] [Non-Patent Document 1] Proc. SPIE 10958, Novel Patterning Technologies for Semiconductors, MEMS / NEMS, and MOEMS 2019, 109580H Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a composition for forming a resist underlayer film capable of forming a resist underlayer film exhibiting excellent processing resistance and excellent gas permeability, a resist underlayer film which is a cured product of a coating film comprising the composition, a method for producing a resist underlayer film using the composition, a pattern formation method, and a method for producing a semiconductor device. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides (A) a polyether compound containing a repeating unit represented by the following general formula (I), (B) an organic solvent; The present invention provides a composition for forming a resist underlayer film, comprising: [ka] (In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected to an aliphatic ring or a heterocycle, or a linear, branched or cyclic hydrocarbon group, or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via an ether group or a carbonyl group; Ar1 may be one type or a combination of multiple types in the same resin; R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, R2 is any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom, and R3 may be one or more types in the same resin and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. n and m are integers of 0 or more.
[0010] The above-mentioned polyether compound contains an aromatic ring in Ar1 in the polymer main chain, and therefore has excellent mechanical strength (also called processing resistance) to withstand processing. On the other hand, by polyetherifying Ar1 using a linear, branched, or cyclic hydrocarbon group, or a heteroalkylene group or an ether group represented by R1 as a linker, it is possible to suppress dense packing between aromatic rings and dense crosslinking reaction, and to suppress the film from becoming dense. By appropriately selecting the main skeleton structure and the substituent structure in this way, it is possible to achieve both the contradictory performances of processing resistance and gas permeability. In addition, since the linker R1 and the ether group can impart fluidity, it is also possible to achieve excellent embedding properties and excellent flatness. Therefore, in the present invention, it is possible to provide a resist underlayer film that is expected to have good film hardness, mechanical strength to withstand processing (good processing resistance), excellent embedding properties and flatness, low film density, and good gas permeability.
[0011] In addition, it is possible to impart thermal fluidity by introducing multiple substituents such as optional R2 and R3. In addition, the steric hindrance of optional substituent R2 or substituents including R3 introduced via an ether structure can further suppress dense packing between aromatic rings and dense crosslinking reactions, thereby further suppressing densification of the film.
[0012] In the above general formula (I), at least one of the R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and wherein the structure R II-1 When the ratio is a, it is preferable that 1≦a≦100. [ka] (In formula (II-1), * represents a bond to an oxygen atom.)
[0013] In the above general formula (I), at least one of R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-1). II-1If the structure R is 1, the packing between aromatic rings can be further suppressed by these steric hindrances, and the membrane can be further prevented from becoming dense. In addition, the hydrophobicity can be increased by sealing the hydroxyl groups, and the affinity with hydrophobic gases such as He and N2 can be increased, thereby improving the permeability of these gases. II-1 Among these, those containing unsaturated bonds can impart crosslinking properties to the compound itself. Therefore, the structure R II-1 By including R3, self-crosslinking is possible, and a hydrophobic resist underlayer film having a low film density can be provided.
[0014] In the above general formula (I), R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 and a structure selected from the group consisting of the structure R II-1 The ratio of the structure R II-2 When the ratio of a to b is taken as b, it is preferable that the relationships 1≦a≦99, 1≦b≦99, and a+b=100 are satisfied. [ka] (In formula (II-1) and formula (II-2), * represents a bond to an oxygen atom.)
[0015] In the above general formula (I), at least one of R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-2). II-2 In this case, since the ring structure has a ring structure, the processing resistance is not easily impaired, while the ring structure itself has a low density, and furthermore, since the steric hindrance is large, the effect of preventing the aromatic rings from being closely adjacent to each other is large, resulting in a film with a low film density. II-1If the unsaturated bond in the compound is contained, the film will be capable of self-crosslinking. In addition, by blocking the hydroxyl group of R3 with these, the polarity of the compound can be reduced, and the gas permeability of hydrophobic He, H2, N2, air, etc. can be improved. Furthermore, by combining multiple substituents in R3, the crystallinity of the resin can be reduced and the thermal fluidity can be improved. In other words, by using a composition containing such a compound, a resist underlayer film can be provided that has low film density, good gas permeability, and excellent processing resistance, embeddability, and flatness.
[0016] In the above general formula (I), R1 is preferably selected from the group consisting of groups represented by the following general formulae (III-1) to (III-3). [ka] (In formulas (III-1) to (III-3), * represents a bond to an oxygen atom.)
[0017] In the above general formula (I), if R1 is selected from the group consisting of the groups represented by the above general formulas (III-1) to (III-3), the composition has a cyclic structure, so that the processing resistance is not easily impaired, while the cyclic structure itself has a low density, and furthermore, the steric hindrance is large, so that the effect of preventing the aromatic rings from being closely adjacent to each other is large, resulting in a film with a low film density. That is, the composition of this preferred embodiment can provide a resist underlayer film that exhibits better processing resistance and higher gas permeability.
[0018] In the above general formula (I), it is preferable that Ar1 is selected from the group consisting of structures represented by the following formula (Ar-1). [ka] (In formula (Ar-1), * represents a bond to the oxygen atom of -O-R1- or OR3.)
[0019] The structures represented by the above formula (Ar-1) each have two benzene rings in one structure, and therefore exhibit good processing resistance. Furthermore, they are bonded or condensed with an alkylene chain or an ether chain, and have, for example, a spiro structure with a three-dimensionally distorted structure, which can suppress packing between aromatic rings, and can suppress the film from becoming dense after baking. As a result, the composition of this preferred embodiment can provide a resist underlayer film with better gas permeability.
[0020] The polyether compound preferably has a weight average molecular weight Mw of 2,000 to 12,000 in terms of polystyrene, as determined by gel permeation chromatography.
[0021] When the weight average molecular weight Mw of the polyether compound is 2000 to 12000, the amount of low molecular weight components that cause sublimate upon baking is reduced, making it difficult for film formation defects to occur, and it is possible to prevent poor embedding properties due to reduced thermal fluidity caused by an excessively large molecular weight from being induced, thereby providing a composition for forming a resist underlayer film.
[0022] The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1; After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, and then the coating film was left for 30 seconds, and then the coating film was spin-dried, and then the coating film was baked at 100°C for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film is FT-2, 101<{(FT-2) / (FT-1)}×100 It is preferable that the above formula is satisfied.
[0023] If the relationship is 101<{(FT-2) / (FT-1)}×100, it indicates that the film after rework has swelled compared to the film immediately after firing. It is believed that immediately after firing, a porous film with many fine pores through which the OK73 thinner can penetrate is formed, suggesting that a film with low film density has been formed rather than a dense film.
[0024] It is preferable that the composition further contains a surfactant (C).
[0025] The composition for forming a resist underlayer film of the present invention contains the surfactant (C), and thus can suppress film formation defects such as striations on the film surface and disturbance of in-plane uniformity.
[0026] (D) a crosslinking agent, The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1; After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, and then the coating film was left for 30 seconds, and then the coating film was spin-dried, and then the coating film was baked at 100°C for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film was FT-2, 100<{(FT-2) / (FT-1)}×100<103 It is also preferable that the above formula is satisfied.
[0027] When the curing of the polyether compound alone is insufficient, the crosslinking agent (D) can accelerate the curing and increase the hardness of the film, strengthening its processing resistance, as well as suppressing the swelling of the film after rework, making it possible to adjust the degree of porosity of the film.
[0028] (E) further comprising a thermally decomposable resin; The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1; After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, and then the coating film was left for 30 seconds, and then the coating film was spin-dried, and then the coating film was baked at 100°C for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film is FT-2, 101.5<{(FT-2) / (FT-1)}×100 It is also preferable that the above formula is satisfied.
[0029] The resist underlayer film forming composition of the present invention further contains a thermally decomposable resin (E), which decomposes when baked and sublimes from within the film, thereby forming further pores within the film. Therefore, in this preferred embodiment of the composition, the swelling of the film after rework increases, making it possible to adjust the degree of porosity of the film.
[0030] (D) a crosslinking agent and (E) a thermally decomposable resin; The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1; After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, and then the coating film was left for 30 seconds, and then the coating film was spin-dried, and then the coating film was baked at 100°C for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film is FT-2, 100<{(FT-2) / (FT-1)}×100 It may be such that:
[0031] Since (D) the crosslinking agent and (E) the thermally decomposable resin have opposing effects in terms of adjusting the porosity of the film, when both are used at the same time, it is sufficient to confirm only the hardening of the film. Therefore, when comparing the difference in film thickness before and after rework, it is sufficient if (FT-2)>(FT-1).
[0032] It is also preferred that the composition further contains an acid generator (F).
[0033] (F) By including an acid generator, it may be possible to enhance the curability of a resin or the decomposition property of a thermally decomposable resin.
[0034] The composition for forming a resist underlayer film of the present invention may be for use in nanoimprinting.
[0035] The use of the resist underlayer film formed by the composition according to the present invention is not particularly limited. For example, the composition for forming a resist underlayer film of the present invention may be for nanoimprinting. The resist underlayer film formed by the composition for forming a resist underlayer film of the present invention has good processing resistance, excellent embedding property and flatness, and further has low film density and good gas permeability. Therefore, the composition of the present invention can realize a resist underlayer film that is very useful for nanoimprinting.
[0036] The present invention also provides a resist underlayer film which is a cured product of a coating film made of the composition for forming a resist underlayer film of the present invention.
[0037] The resist underlayer film formed from the composition for forming a resist underlayer film of the present invention has good processing resistance, excellent embedding property and flatness, and further has low film density and can exhibit good gas permeability.
[0038] In addition, the present invention provides a method for producing a coating film by applying the composition for forming a resist underlayer film of the present invention onto a semiconductor substrate; baking the coating film to obtain a resist underlayer film. The present invention provides a method for producing a resist underlayer film, comprising the steps of:
[0039] Such a method for producing a resist underlayer film of the present invention uses the composition for forming a resist underlayer film of the present invention, and therefore it is possible to realize a resist underlayer film that has good processing resistance, excellent embedding ability and flatness, and further has low film density and good gas permeability.
[0040] The present invention also provides a pattern forming method, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a curable composition film on the resist underlayer film; contacting the curable composition film with a mold; a step of irradiating the curable composition film with light or an electron beam to form a cured film; separating the cured film from the mold; The present invention provides a pattern forming method comprising the steps of:
[0041] According to the pattern formation method by the imprint method of the present invention, a resist underlayer film having good processing resistance, excellent embedding property and flatness, and further having low film density and good gas permeability can be used. Therefore, according to the pattern formation method by the imprint method of the present invention, air bubbles generated when a mold is pressed against a curable composition film can be quickly removed, and a fine pattern can be formed.
[0042] The step of forming a curable composition film on the resist underlayer film may also include forming an adhesion layer and / or a silicone layer containing 99% by mass or less of Si on the resist underlayer film by coating or vapor deposition, and forming a curable composition film thereon.
[0043] By forming an adhesion layer, it is possible to sufficiently suppress pattern peeling during the process of removing the mold. In addition, by forming a silicone layer containing 99 mass % or less of Si, it is possible to adjust the optical properties of the film, enabling reflection control, etc.
[0044] The present invention also provides a method for manufacturing a semiconductor device, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a resist film on the resist underlayer film; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; a step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film; processing the semiconductor substrate using the patterned underlayer film as a mask; The present invention provides a method for manufacturing a semiconductor device, comprising the steps of:
[0045] The present invention also provides a method for manufacturing a semiconductor device, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a hard mask on the resist underlayer film; further forming a resist film on the hard mask; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; Etching the hard mask using the formed resist pattern as a mask to obtain a patterned hard mask; Etching the underlayer film using the patterned hard mask as a mask to obtain a patterned resist underlayer film; processing the semiconductor substrate using the patterned resist underlayer film as a mask; The present invention provides a method for manufacturing a semiconductor device, comprising the steps of:
[0046] The composition for forming a resist underlayer film of the present invention can provide a resist underlayer film that has good processing resistance, excellent embedding property and flatness, and further has low film density and good gas permeability, and is therefore useful in a method for manufacturing a semiconductor device using a pattern formation method other than the nanoimprint method, for example, a multilayer resist method, as described above. That is, according to the method for manufacturing a semiconductor device of the present invention, a fine pattern can be formed on a semiconductor substrate. Effect of the Invention
[0047] As described above, the resist underlayer film forming composition of the present invention is a composition containing (A) a polyether compound having a repeating unit structure represented by the above general formula (I) and (B) an organic solvent, and since the aromatic ring is contained in the polyether compound (A), it can realize sufficient mechanical strength to withstand processing, good embedding property, and good flatness, while the aromatic ring is polyetherified using a linear, branched, or cyclic hydrocarbon group, or a heteroalkylene group or an ether group as a linker, and since the dense packing between the aromatic rings and the dense crosslinking reaction can be inhibited, it is possible to suppress the film from becoming high density. Therefore, the resist underlayer film forming composition of the present invention can provide a resist underlayer film that is good in processing resistance, embedding property, and flatness, has a low film density, and is expected to show good gas permeability.
[0048] In addition, the polyether compound (A) can have multiple substituents, and in particular the ether substituent R3 on the aromatic ring and other substituents R2 can further inhibit packing and dense crosslinking reactions. Furthermore, by having multiple substituents, the crystallinity of the polymer can be suppressed, and it is also possible to impart further thermal fluidity.
[0049] The resist underlayer film forming composition of the present invention may have the film thickness (FT-1) and the film thickness (FT-2) of, for example, 101<{(FT-2) / (FT-1)}×100. This film thickness relationship means that the film is swollen, and represents a porous film having fine pores through which the solvent is impregnated. When a dense curing reaction occurs as in normal resins, there are no gaps through which the solvent is impregnated, so such swelling does not occur, and the film thickness after rework does not become extremely thick. In light of the above, the composition of the present invention is a porous film that is impregnated with the solvent, has a low film density, and gases, like the solvent, also seep into and penetrate the film.
[0050] Furthermore, the resist underlayer film of the present invention exhibits good processing resistance, excellent embedding ability and flatness, and further has a low film density and exhibits good gas permeability.
[0051] Furthermore, according to the method for forming a resist underlayer film of the present invention, it is possible to produce a resist underlayer film that exhibits good processing resistance, excellent embedding ability and flatness, as well as low film density and good gas permeability.
[0052] Furthermore, according to the pattern forming method of the present invention, air bubbles generated when the mold is pressed against the curable composition film can be quickly removed, and a fine pattern can be formed.
[0053] Furthermore, according to the method for manufacturing a semiconductor device of the present invention, a semiconductor device having a fine pattern formed on a semiconductor substrate can be manufactured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] As described above, in order to form a resist underlayer film capable of transferring a resist pattern to a substrate to be processed with higher accuracy in a fine patterning process, there has been a demand for the development of a resist underlayer film that is excellent in processing resistance, embeddability, and flatness, as well as high gas permeability.
[0055] The present inventors focused on aromatic ring-containing polymers that have sufficient mechanical strength but form dense films by packing, and considered the introduction of a structure that inhibits packing and conducted intensive research. As described above, photo-nanoimprinting technology that can form fine structures on the order of several nanometers on a substrate has attracted attention, but there is a problem that defects occur due to bubbles that are generated when the mold is pressed, and improvements have been made to the gas permeability of the mold side to date. On the other hand, in consideration of future miniaturization, the current improvements on the mold side alone are insufficient, and it is thought that bubbles can be eliminated from the resist underlayer film side as well, but material development has not progressed and there are still few material options. The present inventors considered that by polyetherifying a phenolic hydroxyl group-containing aromatic compound as a core with a linear, branched, or cyclic hydrocarbon group or a heteroalkylene group and an ether group as a linker, the aromatic ring can provide sufficient mechanical strength, and the linker's hydrocarbon group, heteroalkylene group, or ether group can provide fluidity and suppress packing of the aromatic ring, thereby resulting in a film with good embedding property and flatness, low film density, and excellent gas permeability.Furthermore, by etherifying the unreacted hydroxyl group that has not reacted during polyetherification, it is possible to further improve fluidity and suppress packing, resulting in a composition for forming a resist underlayer film that shows even better embedding property, flatness, and gas permeability.
[0056] Based on this idea, the present inventors have conducted further intensive research and found that a composition containing (A) a polyether compound containing a repeating unit represented by the following general formula (I) and (B) an organic solvent can provide a composition for forming a resist underlayer film that has mechanical strength sufficient to withstand processing, is excellent in embedding ability and flatness, and is capable of realizing a resist underlayer film having low film density and good gas permeability, thereby completing the present invention.
[0057] That is, the present invention provides (A) a polyether compound containing a repeating unit represented by the following general formula (I), (B) an organic solvent; The composition for forming a resist underlayer film is characterized by comprising: [ka] (In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected to an aliphatic ring or a heterocycle, or a linear, branched or cyclic hydrocarbon group, or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via an ether group or a carbonyl group; Ar1 may be one type or a combination of multiple types in the same resin; R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, R2 is any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom, and R3 may be one or more types in the same resin and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. n and m are integers of 0 or more.
[0058] The present invention will be described in detail below, but the present invention is not limited thereto.
[0059] <Composition for forming resist underlayer film> The composition for forming a resist underlayer film for nanoimprinting of the present invention comprises: (A) a polyether compound having a repeating unit represented by the following general formula (I); (B) an organic solvent; The composition for forming a resist underlayer film is characterized by comprising: [ka] (In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected to an aliphatic ring or a heterocycle, or a linear, branched or cyclic hydrocarbon group, or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via an ether group or a carbonyl group; Ar1 may be one type or a combination of multiple types in the same resin; R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, R2 is any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom, and R3 may be one or more types in the same resin and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. n and m are integers of 0 or more.
[0060] The above-mentioned polyether compound contains an aromatic ring in Ar1 in the polymer main chain, and therefore has excellent mechanical strength (also called processing resistance) to withstand processing. On the other hand, by polyetherifying Ar1 using a linear, branched, or cyclic hydrocarbon group, or a heteroalkylene group or an ether group represented by R1 as a linker, it is possible to suppress dense packing between aromatic rings and dense crosslinking reaction, and to suppress the film from becoming dense. By appropriately selecting the main skeleton structure and the substituent structure in this way, it is possible to achieve both the contradictory performances of processing resistance and gas permeability. In addition, since the linker R1 and the ether group can impart fluidity, it is also possible to achieve excellent embedding properties and excellent flatness. Therefore, in the present invention, it is possible to provide a resist underlayer film that is expected to have good film hardness, mechanical strength to withstand processing (good processing resistance), excellent embedding properties and flatness, low film density, and good gas permeability.
[0061] In addition, it is possible to impart thermal fluidity by introducing multiple substituents such as R2 and R3. In addition, the steric hindrance of any substituent R2 or a substituent including R3 introduced via an ether structure can further suppress dense packing between aromatic rings and dense crosslinking reactions, thereby further suppressing densification of the film.
[0062] According to the composition for forming a resist underlayer film of the present invention, a resist underlayer film that can be used in various pattern forming methods can be formed. For example, the resist underlayer film formed from the composition for forming a resist underlayer film of the present invention can be used as a resist underlayer film in a pattern forming method by a multilayer resist process, can be used as a resist underlayer film in a pattern forming method by a nanoimprint method, and can also be used in other pattern forming methods. In particular, as described above, the resist underlayer film formed from the composition for forming a resist underlayer film of the present invention has good processing resistance, excellent embedding property and flatness, and further has low film density and good gas permeability. Therefore, according to the composition for forming a resist underlayer film of the present invention, a resist underlayer film that is very useful for nanoimprint can be realized.
[0063] Hereinafter, each component of the composition for forming a resist underlayer film of the present invention will be described in more detail.
[0064] <(A) Polyether compound> In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected with an aliphatic ring or heterocycle, or a linear, branched or cyclic hydrocarbon group, an ether group or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via a carbonyl group, and Ar1 may be one type or a combination of a plurality of types in the same resin. From the viewpoint of increasing strength against processing, Ar1 is preferably naphthalene rather than benzene, and anthracene rather than naphthalene, and from the viewpoint of gas permeability, it is preferable that a plurality of benzenes and / or naphthalenes are condensed or connected with a linear, branched or cyclic alkylene group or an ether group.
[0065] In the above general formula (I), R2 is any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom. From the viewpoint of suppressing packing, R2 is preferably a hydrocarbon group, and from the viewpoint of maintaining processing resistance, it is more preferably a cyclic hydrocarbon group. From the viewpoint of increasing the hydrophobicity of the film, R2 is preferably a halogen atom, and particularly preferably a fluorine atom.
[0066] In the above general formula (I), specific examples of the structure of Ar1 including R2 include, but are not limited to, the structures shown below. (* represents a bond to an oxygen atom in the polymer main chain or a bond to an oxygen atom of an optional substituent OR3.)
[0067] [ka]
[0068] [ka]
[0069] [ka]
[0070] In the above general formula (I), R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic heteroalkylene group having 1 to 20 carbon atoms. From the viewpoint of suppressing packing of aromatic rings and maintaining processing resistance, R1 is preferably a cyclic hydrocarbon group or a heteroalkyl group. In addition, from the viewpoint of thermosetting, R1 preferably contains an unsaturated bond. Furthermore, multiple R1s can be used in combination in the same resin. By combining multiple R1s, improvement of solubility and improvement of thermal fluidity can be expected.
[0071] In the above general formula (I), specific examples of the structure of R1 include, but are not limited to, the following structures: (* represents the bond to the oxygen atom.)
[0072] [ka]
[0073] In the above general formula (I), it is particularly preferable that R1 is selected from the group consisting of groups represented by the following general formulae (III-1) to (III-3). [ka] (In formulas (III-1) to (III-3), * represents a bond to an oxygen atom.)
[0074] In the above general formula (I), if R1 is selected from the group consisting of the groups represented by the above general formulas (III-1) to (III-3), the composition has a cyclic structure, so that the processing resistance is not easily impaired, while the cyclic structure itself has a low density, and furthermore, the steric hindrance is large, so that the effect of preventing the aromatic rings from being closely adjacent to each other is large, resulting in a film with a low film density. That is, the composition of this preferred embodiment can provide a resist underlayer film that exhibits better processing resistance and higher gas permeability.
[0075] In the above general formula (I), R3 may be one or more combinations in the same resin, and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. From the viewpoint of thermosetting, R3 is preferably an alkenyl group or an alkynyl group. In addition, R3 is preferably a branched or cyclic alkyl group from the viewpoint of suppressing packing of aromatic rings, and more preferably a cyclic alkyl group from the viewpoint of maintaining processing resistance.
[0076] In the above general formula (I), specific examples of the structure of R3 include, but are not limited to, the following structures: (* represents the bond to the oxygen atom.)
[0077] [ka]
[0078] In the above general formula (I), at least one of the R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and wherein the structure R II-1 When the ratio is a, it is preferable that 1≦a≦100. [ka] (In formula (II-1), * represents a bond to an oxygen atom.)
[0079] In the above general formula (I), at least one of R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-1). II-1 If the structure R is 1, the packing between aromatic rings can be further suppressed by these steric hindrances, and the membrane can be further prevented from becoming dense. In addition, the hydrophobicity can be increased by sealing the hydroxyl groups, and the affinity with hydrophobic gases such as He and N2 can be increased, thereby improving the permeability of these gases. II-1 Among these, those containing unsaturated bonds can impart crosslinking properties to the compound itself. Therefore, the structure R II-1 By including R3, self-crosslinking is possible, and a hydrophobic resist underlayer film having a low film density can be provided.
[0080] In addition, in the above general formula (I), R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 and a structure selected from the group consisting of the structure R II-1 The ratio of the structure R II-2 When the ratio of a to b is taken as the ratio of a to b, it is also preferable that the relationships 1≦a≦99, 1≦b≦99, and a+b=100 are satisfied. [ka] (In formula (II-1) and formula (II-2), * represents a bond to an oxygen atom.)
[0081] In the above general formula (I), at least one of R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-2). II-2In this case, since the ring structure has a ring structure, the processing resistance is not easily impaired, while the ring structure itself has a low density, and furthermore, since the steric hindrance is large, the effect of preventing the aromatic rings from being closely adjacent to each other is large, resulting in a film with a low film density. II-1 If the unsaturated bond in the compound is contained, the film will be capable of self-crosslinking. In addition, by blocking the hydroxyl group of R3 with these, the polarity of the compound can be reduced, and the gas permeability of hydrophobic He, H2, N2, air, etc. can be improved. Furthermore, by combining multiple substituents in R3, the crystallinity of the resin can be reduced and the thermal fluidity can be improved. In other words, by using a composition containing such a compound, a resist underlayer film can be provided that has low film density, good gas permeability, and excellent processing resistance, embeddability, and flatness.
[0082] In the above general formula (I), R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-1) from the viewpoint of thermosetting properties. II-1 In terms of maintaining the processing resistance, reducing the film density, and improving the thermal fluidity, it is preferable that the structure R be selected from the group consisting of the groups represented by the above general formula (II-2). II-2 Therefore, it is preferable that the structure R3 is included in R3 in a proportion that ensures the curability of the composition. II-1 If R3 is included, the remaining R3 is a structure R selected from the group consisting of the groups shown in general formula (II-2) above. II-2 That is, the structure R II-1 and structure R II-2 The ratio of the combination of structures selected from the above is preferably a ratio that can ensure curability at the very least with the resin alone, and specifically, it is preferable to satisfy the relationships of 1≦a≦99, 1≦b≦99, and a+b=100, it is more preferable to satisfy the relationships of 30≦a≦90, a+b=100, and it is particularly preferable to satisfy the relationships of 50≦a≦80, a+b=100.
[0083] In the above general formula (I), n and m are integers of 0 or more. From the viewpoint of imparting thermosetting properties and steric hindrance by the ether structure, n is preferably 1 or more and 2 or less. m is more preferably 0 or more and 4 or less. For the same reason as n, m is also preferably 2 or more, but may be 0 from the viewpoint of availability of raw materials.
[0084] For example, in the above general formula (I), Ar1 is preferably selected from the group consisting of structures represented by the following formula (Ar-1). [ka] (In formula (Ar-1), * represents a bond to the oxygen atom of -O-R1- or OR3.)
[0085] Since the structures represented by the above formula (Ar-1) each have two benzene rings in one structure, it is expected to show good processing resistance. Furthermore, it is bonded or condensed with a linear, branched, or cyclic alkylene chain or ether chain, and has, for example, a spiro structure having a three-dimensionally distorted structure, which can suppress packing between aromatic rings, and can suppress the film from becoming dense after baking. As a result, the composition of this preferred embodiment can provide a resist underlayer film that has a low film density after baking and shows better gas permeability.
[0086] When the same resin of the polyether compound (A) has multiple combinations of Ar1, the polyether compound (A) may contain multiple repeating units with different Ar1 in the same resin. Similarly, when the same resin of the polyether compound (A) has multiple combinations of R3, the polyether compound (A) may contain multiple repeating units with different R3 in the same resin.
[0087] <Synthesis method> The polyether compound (A) can be synthesized, for example, by carrying out a polyetherification reaction (STEP 1) using a hydroxyl group-containing derivative of Ar1 (X), a reagent X-R1-X (Y) which is an alkyl dihalide, alkyl ditosylate, or alkyl dimesylate, and a catalyst, and then carrying out etherification (STEP 2) using the polymer obtained by polyetherification, a reagent R3-X (Z) which is an alkyl halide, alkyl tosylate, or alkyl mesylate, and a catalyst. (R1, R2, R3, n, and m are the same as above, and X is a halogen group, a mesyl group, or a tosyl group. Two or more types of R3-X may be used, but for convenience of explanation, only one type is described.)
[0088] (STEP 1) [ka]
[0089] (STEP 2) [ka]
[0090] In addition, the amount of reagent (Y) used when carrying out the above (STEP 1) is preferably 0.6 to 0.95 equivalents relative to derivative (X), and more preferably 0.7 to 0.9 equivalents. When the amount of reagent (Y) used is within the preferred range, some hydroxyl groups that are not consumed in polyetherification will remain after the completion of (STEP 1). For example, as shown in the following formula, when 1 equivalent of resorcinol (2 equivalents of hydroxyl groups) as derivative (X) is reacted with 0.9 equivalents of dibromobutane (1.8 equivalents of reaction sites with hydroxyl groups) as reagent (Y), 0.2 equivalents of hydroxyl groups that are not consumed in polyetherification will remain. When 1 equivalent of phloroglucinol (3 equivalents of hydroxyl groups) as derivative (X) is reacted with 0.9 equivalents of dibromohexane (1.8 equivalents of reaction sites with hydroxyl groups) as reagent (Y), 1.2 equivalents of hydroxyl groups that are not consumed in polyetherification will remain. In particular, in the case of phloroglucinol, for the sake of convenience, it is described as if one hydroxyl group is not involved in polyetherification, but in reality, there are some that are not involved in polyetherification, some that are involved in polyetherification at only one position, and some that are involved in polyetherification at all three positions. These hydroxyl group residues can be etherified by the above (STEP 2). For resorcinol, a reaction example is shown in which propargyl bromide is used as the reagent (Z), and for flurglucinol, a reaction example is shown in which propargyl bromide and two types of bromohexane are used as the reagents (Z).
[0091] (STEP 1 for resorcinol) [ka]
[0092] (STEP 1 for phloroglucinol) [ka]
[0093] (Step 2 for resorcinol) [ka]
[0094] (STEP 2 in the case of phloroglucinol) [ka]
[0095] The polyetherification reaction using the above-mentioned derivative (X), reagent (Y), and catalyst can usually be carried out without a solvent or in a solvent using a base as a catalyst at room temperature or, if necessary, under cooling or heating. Examples of the solvent used in STEP 1 include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; lactones such as γ-butyrolactone; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoric triamide, and N-methylpyrrolidone. As the solvent, one of these may be used alone, or two or more may be used in combination. These solvents can be used in an amount of, for example, 0 to 3000 parts by mass per 100 parts by mass of the reaction raw materials.
[0096] Examples of the base catalyst used in STEP 1 include inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, and calcium hydride; alkyl metals such as methyl lithium, n-butyl lithium, methyl magnesium chloride, and ethyl magnesium bromide; alkoxides such as sodium methoxide, sodium ethoxide, and potassium t-butoxide; and organic bases such as triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, and 4-dimethylaminopyridine. The amount of the catalyst used is, for example, 0.1 to 1.5 equivalents relative to the amount of hydroxyl groups in the raw material, and preferably 1.0 to 1.05 equivalents. The reaction temperature is preferably from -50°C to the boiling point of the solvent, and more preferably from room temperature to 130°C.
[0097] The polyetherification reaction (STEP 1) may be carried out by adding the derivative (X), the reagent (Y), and the catalyst all at once, by dropping a solution of the reagent (Y) or the reagent (Y) dissolved in the reaction solvent in the presence of the derivative (X) and the catalyst, or by dropping a solution of the derivative (X) or the derivative (X) dissolved in the reaction solvent in the presence of the reagent (Y) and the catalyst. After the polyetherification reaction is completed, the reagent (Z) or the solution of the reagent (Z) dissolved in the reaction solvent may be dropped to perform the etherification in STEP 2 continuously, but in order to remove the unreacted raw materials and catalysts present in the system, the temperature of the reaction vessel may be increased to 130 to 230°C and the volatile matter may be removed at about 1 to 50 mmHg, or an appropriate poor solvent or water may be added to precipitate or fractionate the polymer. These methods can be used depending on the amount and properties of the raw materials used and the reaction product obtained. In addition, a process of dissolving the obtained polyether compound in an appropriate solvent such as methyl isobutyl ketone or ethyl acetate and washing with water may be added.
[0098] The etherification after the polyetherification (STEP 2) can also be carried out, for example, without a solvent or in a solvent using a base as a catalyst at room temperature or, if necessary, under cooling or heating. Examples of the solvent used in STEP 2 include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; lactones such as γ-butyrolactone; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoric triamide, and N-methylpyrrolidone. As the solvent, one of these may be used alone, or two or more may be used in combination. These solvents can be used in an amount of 0 to 2,000 parts by mass per 100 parts by mass of the reaction raw materials.
[0099] Examples of the base catalyst used in STEP 2 include inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, and calcium hydride; alkyl metals such as methyllithium, n-butyllithium, methylmagnesium chloride, and ethylmagnesium bromide; alkoxides such as sodium methoxide, sodium ethoxide, and potassium t-butoxide; and organic bases such as triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, and 4-dimethylaminopyridine. The amount of the catalyst used is preferably 0.1 to 1.5 equivalents relative to the amount of hydroxyl groups contained in the raw material, and more preferably 1.0 to 1.2 equivalents. The reaction temperature is preferably from -50°C to the boiling point of the solvent, and more preferably from room temperature to 130°C.
[0100] The reaction method includes a method of charging the polyether compound, the reagent (Z) and the catalyst all at once, a method of dropping the polyether compound and the catalyst, the reagent (Z) or a solution of the reagent (Z) dissolved in a reaction solvent, or a method of dropping the polyether compound and the reagent (Z) dissolved in a reaction solvent in the presence of the catalyst. In this case, the amount of the reagent (Z) used is preferably 1.0 to 1.2 equivalents relative to the amount of hydroxyl group residues of the polyether compound, more preferably 1.0 to 1.05 equivalents. In addition, when using multiple types of reagents (Z), a method can be selected in which a reagent (Z) with a large steric hindrance at the reaction site and low reactivity such as bromomethylcyclohexane is added first and aged, and then a reagent (Z) with a small steric hindrance at the reaction site and high reactivity such as propargyl bromide is added later, or a method can be selected in which a reagent (Z) with a high boiling point such as mesyl or tosylate that cannot be removed under reduced pressure after the reaction is added first and aged, and then a small excess amount of a reagent (Z) with a low boiling point such as propargyl bromide or bromopropene that can be removed under reduced pressure after the reaction is added later to increase the substitution rate. After the etherification is completed, in order to remove unreacted raw materials, catalysts, etc. present in the system, the temperature of the reaction vessel is raised to 130 to 230 ° C. and volatiles are removed at about 1 to 50 mmHg, or an appropriate poor solvent or water is added to precipitate or fractionate the polymer, and the like, and the treatment can be performed according to the properties of the raw materials used and the obtained reaction product. In addition, a process may be added in which the resulting polyether compound (A) is dissolved in a suitable solvent such as methyl isobutyl ketone or ethyl acetate, and then acid-washed with an aqueous solution of a suitable acid such as nitric acid or hydrochloric acid, followed by washing with ultrapure water to remove metal species such as sodium and potassium.
[0101] The polystyrene-equivalent weight average molecular weight Mw of the polyether compound (A) obtained by the above-mentioned synthesis method, as determined by gel permeation chromatography, is preferably 2,000 to 12,000, more preferably 2,000 to 8,000, from the viewpoints of embeddability and suppression of sublimate.
[0102] When the weight average molecular weight Mw of the (A) polyether compound is 2000 to 12000, the amount of low molecular weight components that sublimate upon baking is reduced, and an underlayer film that does not impair embedding properties is obtained; when the weight average molecular weight Mw is 2000 to 8000, this effect is even greater.
[0103] <(B) Organic solvent> The (B) organic solvent that can be used is not particularly limited as long as it can dissolve the (A) polyether compound and, if contained, the (C) surfactant, (D) crosslinking agent, (E) thermally decomposable resin, (F) acid generator, and other additives, which will be described later.
[0104] Specifically, the organic solvents described in paragraphs
[0091] to
[0092] of JP 2007-199653 A can be added. More specifically, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, cyclohexanone, γ-butyrolactone, or a mixture containing one or more of these is preferably used.
[0105] The amount of the organic solvent to be added is preferably within a range of 200 to 10,000 parts, and more preferably 250 to 5,000 parts, based on 100 parts by mass of the (A) polyether compound.
[0106] In addition, in the composition for forming a resist underlayer film of the present invention, the (B) organic solvent may be used as a mixture of one or more organic solvents having a boiling point of less than 180°C ((B1) low boiling point solvent) and one or more organic solvents having a boiling point of 180°C or higher ((B2) high boiling point solvent).
[0107] The high boiling point solvent is not particularly limited as long as it can dissolve each component of the composition for forming a resist underlayer film of the present invention, and may be any of hydrocarbons, alcohols, ketones, esters, ethers, chlorine-based solvents, etc., specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-Hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerin, n-nonyl acetate, monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol-n-butyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol diacetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,Examples of the high boiling point solvent include 6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, and dibutyl adipate. These may be used alone or in combination as the (B2) high boiling point solvent.
[0108] The high boiling point solvent may be appropriately selected from the above-mentioned solvents according to the temperature at which the resist underlayer film forming composition of the present invention is heat-treated. The boiling point of the high boiling point solvent is preferably 180°C to 300°C, more preferably 200°C to 300°C. If the solvent has such a boiling point, there is no risk of the solvent volatilizing too quickly when baked (heat-treated), so that it is possible to obtain sufficient thermal fluidity during film formation and form a resist underlayer film having excellent filling and flattening properties. In addition, if the solvent has such a boiling point, there is no risk of the solvent remaining in the film without volatilizing after baking, so there is no risk of adversely affecting the film properties such as filling properties.
[0109] When a high boiling point solvent is used, the blending amount is preferably 1 to 30 parts by mass per 100 parts by mass of an organic solvent having a boiling point of less than 180° C. Such a blending amount is preferable because it can impart sufficient thermal fluidity during baking and does not remain in the film, leading to deterioration of film properties such as embedding characteristics.
[0110] <Optional ingredients> The composition for forming a resist underlayer film of the present invention may further contain optional components other than the polyether compound (A) and the organic solvent (B). The optional components are described below.
[0111] <(C) Surfactant> The composition of the present invention may contain (C) a surfactant. To the composition for forming a resist underlayer film of the present invention, a surfactant (C) can be added in order to improve the coating property in spin coating. As the surfactant, for example, those described in
[0142] to
[0147] of JP-A-2009-269953 can be used. When a surfactant is added, the amount of the surfactant is preferably 0.01 to 10 parts, more preferably 0.05 to 5 parts, based on 100 parts by mass of the above-mentioned (A) reactant.
[0112] [(D) Crosslinking agent] The composition for forming a resist underlayer film of the present invention may contain (D) a crosslinking agent.
[0113] (D) Crosslinking agent promotes crosslinking within the membrane, and because of its aromatic ring structure, it is closely adjacent to (A) polyether compound, which increases the density of the membrane. Therefore, there are fewer holes for the solvent to penetrate, and swelling of the membrane after rework is suppressed. Therefore, crosslinking agents can be added as crosslinking promoters, processing resistance improvers, and even as membrane swelling inhibitors.
[0114] The (D) crosslinking agent is not particularly limited, and various known crosslinking agents can be widely used. Examples include melamine-based crosslinking agents, acrylate-based crosslinking agents, glycoluril-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, epoxy-based crosslinking agents, and phenol-based crosslinking agents (e.g., methylol or alkoxymethyl-type crosslinking agents of polynuclear phenols). The content of the (D) crosslinking agent is preferably 5 to 50 parts by mass, more preferably 10 to 40 parts by mass, relative to 100 parts by mass of the (A) polyether compound.
[0115] Specific examples of the melamine-based crosslinking agent include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy- and / or hydroxy-substituted products thereof, and partial self-condensates thereof.
[0116] A specific example of the acrylate crosslinking agent is dipentaerythritol hexaacrylate.
[0117] Specific examples of glycoluril crosslinking agents include tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, alkoxy and / or hydroxy substituted products thereof, and partial self-condensates thereof.
[0118] Specific examples of benzoguanamine-based crosslinking agents include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy- and / or hydroxy-substituted products thereof, and partial self-condensates thereof.
[0119] Specific examples of the urea-based crosslinking agent include dimethoxymethylated dimethoxyethyleneurea, its alkoxy and / or hydroxyl substituted derivatives, and partial self-condensates thereof.
[0120] A specific example of the β-hydroxyalkylamide crosslinking agent is N,N,N',N'-tetra(2-hydroxyethyl)adipamide.
[0121] Specific examples of the isocyanurate crosslinking agent include triglycidyl isocyanurate and triallyl isocyanurate.
[0122] Specific examples of the aziridine crosslinking agent include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate].
[0123] Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tertbutyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymer.
[0124] Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0125] Specific examples of polynuclear phenol-based crosslinking agents include compounds represented by the following general formula (XL-1).
[0126] [ka] (In the formula, L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R4 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. q is an integer of 1 to 5.)
[0127] L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. q is an integer of 1 to 5, and is more preferably 2 or 3. Specific examples of L include groups obtained by removing q hydrogen atoms from methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane. R4 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. Specific examples of the alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, an isopentyl group, a hexyl group, an octyl group, an ethylhexyl group, a decyl group, and an eicosanyl group, and a hydrogen atom or a methyl group is preferable.
[0128] Specific examples of the compound represented by the above general formula (XL-1) include the following compounds. Among these, from the viewpoint of improving the curability and thickness uniformity of the organic film, hexamethoxymethylated triphenolmethane, triphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are preferred. R4 is the same as above.
[0129] [ka]
[0130] [ka]
[0131] <(E) Thermally decomposable resin> In addition, the composition for forming a resist underlayer film of the present invention may contain (E) a thermally decomposable resin from the viewpoint of reducing the film density. By containing (E) a thermally decomposable resin, the thermally decomposable resin decomposes during baking and sublimes from within the film, thereby forming minute pores within the film. As a result, the swelling of the film after rework increases, making it possible to increase the porosity of the film.
[0132] As the (E) thermally decomposable resin, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer (resin) having a weight loss rate of 40% or more from 30° C. to 250° C. and a weight average molecular weight of 300 to 200,000 is preferably used. This thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by any one of the following general formulas (DP1), (DP1a) to (DP3a).
[0133] [ka] (In the formula, R 1 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. W is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.
[0134] [ka] (In formulas (DP1a) to (DP3a), R 1a is an alkyl group having 1 to 4 carbon atoms. a R is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, which may have an ether bond. b1 are each independently, -W a R is —OH or a saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms which may be substituted. 1c R is a hydrogen atom, or an optionally substituted aryl group having 6 to 20 carbon atoms or a optionally substituted heteroaryl group having 4 to 20 carbon atoms. c1each independently represents an alkyl group having 1 to 4 carbon atoms, or -W a -OH. n represents the average number of repeating units and is 3 to 500.
[0135] Specific examples of the thermally decomposable resin include, but are not limited to, those shown below.
[0136] [ka]
[0137] [ka]
[0138] [ka]
[0139] [ka] (n represents the average number of repeating units and is 3 to 500).
[0140] When the (E) thermally decomposable resin is added, the amount added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the (A) polyether compound.
[0141] <(F) Acid Generator> In the resist underlayer film forming composition of the present invention, an acid generator can be added to further promote the curing reaction of the polyether compound (A). The acid generator may be one that generates an acid by thermal decomposition (thermal acid generator) or one that generates an acid by light irradiation (photoacid generator), and any of these may be added. Specifically, the materials described in paragraphs
[0061] to
[0085] of JP-A-2007-199653 may be added, but are not limited thereto.
[0142] The acid generator may be used alone or in combination of two or more. When an acid generator is added, the amount of the acid generator is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the (A) polyether compound.
[0143] [Film density properties] The resist underlayer film forming composition of the present invention is preferably such that, for example, the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is baked at 180°C for 60 seconds, and then additionally baked at 350°C for 60 seconds, the thickness of the coating film after that is FT-1, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is dispensed onto the coating film after additional baking, then the coating film is left for 30 seconds, then the coating film is spin-dried, and then the coating film is baked at 100°C for 60 seconds to evaporate the OK73 thinner, and the thickness of the coating film after that is FT-2 is 101<{(FT-2) / (FT-1)}×100.
[0144] If 101<{(FT-2) / (FT-1)}×100, the film immediately after firing is porous with many pores that allow the OK73 thinner to soak in, and the larger the value, the more porous and low-density the film is. Therefore, when considering gas permeability, it is preferable that 101<{(FT-2) / (FT-1)}×100, and more preferably 101.5<{(FT-2) / (FT-1)}×100.
[0145] When the composition further contains a crosslinking agent (D), it is preferable that the composition satisfies the following relationship: 100<{(FT-2) / (FT-1)}×100<103. As mentioned above, the crosslinking agent (D) has the effect of increasing the density of the film. Therefore, there are fewer holes through which the solvent can penetrate, and the swelling of the film after rework is suppressed. Therefore, the crosslinking agent can be added as a crosslinking promoter and also as a swelling suppressor of the film.
[0146] When the composition further contains (E) a thermally decomposable resin, it is preferable that the composition has a ratio of 101.5<{(FT-2) / (FT-1)}×100. By containing (E) a thermally decomposable resin, the thermally decomposable resin decomposes during baking and sublimes from within the film, thereby forming minute pores within the film. As a result, the swelling of the film after rework increases, which makes it possible to increase the porosity of the film and reduce the film density.
[0147] When the composition further contains both the crosslinking agent (D) and the thermally decomposable resin (E), it is also preferable that the relationship satisfies 100<{(FT-2) / (FT-1)}×100.
[0148] (D) Crosslinking agent and (E) thermally decomposable resin have opposing effects as film density adjusters. Therefore, when using both at the same time, it is sufficient to confirm only the hardening of the film. When comparing the difference in film thickness before and after rework, it is sufficient if (FT-2)>(FT-1).
[0149] Hereinafter, a method for producing a resist underlayer film, a method for forming a pattern, and a method for producing a semiconductor device using the resist underlayer film forming composition according to the present invention will be described.
[0150] [Method of manufacturing resist underlayer film] The method for producing a resist underlayer film of the present invention comprises the steps of: Applying the composition for forming a resist underlayer film of the present invention onto a semiconductor substrate to obtain a coating film; baking the coating film to obtain a resist underlayer film. Includes.
[0151] Semiconductor substrates, e.g., substrates used in the manufacture of semiconductor devices, include, for example, silicon wafer substrates, silicon / silicon dioxide coated substrates, silicon nitride substrates, glass substrates, ITO substrates, polyimide substrates, and low dielectric constant material (low-k material) coated substrates.
[0152] The resist underlayer film forming composition of the present invention is applied onto this semiconductor substrate by an appropriate application method such as using a spinner or a coater to obtain a coating film.
[0153] Thereafter, the coating film is baked to form a resist underlayer film.
[0154] The firing conditions are appropriately selected from a firing temperature of 80°C to 400°C and a firing time of 0.3 to 60 minutes. Preferably, the firing temperature is 150°C to 350°C and the firing time is 0.5 to 2 minutes, and more preferably, a two-stage firing is performed by firing at a firing temperature of 100°C to 200°C for 0.5 to 2 minutes, followed by additional firing at 200°C to 350°C for 0.5 to 2 minutes. Here, the film thickness of the lower layer film formed is, for example, 10 to 1500 nm, and more preferably 500 nm to 1000 nm. Furthermore, if a quartz substrate is used as the substrate, a replica (mold replica) of the quartz imprint mold can be produced.
[0155] Also, an adhesion layer and / or a silicone layer containing 99% by mass or less or 50% by mass or less of Si can be formed by coating or vapor deposition on the resist underlayer film formed as described above. For example, in addition to the adhesion layer described in JP-A-2013-202982 and JP-A-5827180 and the method of forming a silicon-containing resist underlayer film (inorganic resist underlayer film) forming composition described in WO2009 / 104552A1 by spin coating, a Si-based inorganic material film can be formed by a CVD method or the like.
[0156] In addition, as described above, the resist underlayer film forming composition according to the present invention can form an underlayer film exhibiting improved flatness. For example, the resist underlayer film forming composition according to the present invention can be applied onto a semiconductor substrate having a portion with a step and a portion without a step (so-called stepped substrate) to obtain a coating film, and the coating film can be baked to form a resist underlayer film in which the step between the portion with a step and the portion without a step is within the range of 3 to 100 nm.
[0157] [Pattern formation method] The pattern forming method according to the present invention comprises the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a curable composition film on the resist underlayer film; contacting the curable composition film with a mold; a step of irradiating the curable composition film with light or an electron beam to form a cured film; separating the cured film from the mold; Includes.
[0158] This pattern formation method is called an imprint method using a mold. The imprint method may be a nanoimprint method. According to the pattern formation method by the imprint method of the present invention, a resist underlayer film having good processing resistance, excellent embedding property and flatness, and further having low film density and good gas permeability can be used. Therefore, according to the pattern formation method by the imprint method of the present invention, air bubbles generated when the mold is pressed against the curable composition film can be quickly removed, and a fine pattern can be formed.
[0159] Each step will be described in more detail below.
[0160] <Step of forming resist underlayer film> In this step, for example, a resist underlayer film can be formed on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention by the method for producing a resist underlayer film of the present invention described above.
[0161] <Step of forming a curable composition film> This step is a step of forming a curable composition film on the resist underlayer film.
[0162] The composition of the curable composition film formed on the resist underlayer film is not particularly limited as long as it is sensitive to the light used for exposure. Both negative photoresists and positive photoresists can be used. There are positive photoresists made of novolac resin and 1,2-naphthoquinone diazide sulfonic acid ester, chemically amplified photoresists made of a binder having a group that decomposes with acid to increase the alkaline dissolution rate and a photoacid generator, chemically amplified photoresists made of a low molecular compound that decomposes with acid to increase the alkaline dissolution rate of the photoresist, an alkali-soluble binder, and a photoacid generator, and chemically amplified photoresists made of a binder having a group that decomposes with acid to increase the alkaline dissolution rate, a low molecular compound that decomposes with acid to increase the alkaline dissolution rate of the photoresist, and a photoacid generator. Examples of such photoresists include APEX-E (trade name) manufactured by Shipley, PAR710 (trade name) manufactured by Sumitomo Chemical Co., Ltd., and SEPR430 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd. Further, there can be mentioned fluorine-containing polymer photoresists as described in, for example, Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).
[0163] [Method of applying the curable composition] Examples of methods for applying the curable composition include inkjet printing, dip coating, air knife coating, curtain coating, wire bar coating, gravure coating, extrusion coating, spin coating, and slit scanning. Inkjet printing is suitable for applying the curable composition as droplets, and spin coating is suitable for coating the curable composition. In this step, an adhesion layer and / or a silicone layer containing 99% by mass or less or 50% by mass or less of Si may be formed on the nanoimprint resist underlayer film by coating or vapor deposition, and the curable composition may be applied thereon.
[0164] In the step of forming the curable composition film, an adhesion layer and / or a silicone layer containing 99 mass % or less of Si can also be formed on the resist underlayer film by coating or vapor deposition.
[0165] By forming an adhesion layer, it is possible to sufficiently suppress pattern peeling in the subsequent mold separation process. In addition, by forming a silicone layer containing 99 mass % or less of Si, it is possible to adjust the optical properties of the film, enabling reflection control, etc.
[0166] <Step of bringing the curable composition film into contact with the mold> In this step, the curable composition film is brought into contact with a mold. For example, when the liquid curable composition film is brought into contact with a mold having a prototype pattern for transferring a pattern shape, a liquid film is formed in which the curable composition fills the recesses of the fine pattern on the mold surface.
[0167] Considering the process of irradiating light or electron beams described later, it is recommended to use a mold having a light-transmitting material as a substrate. Specifically, the mold substrate is preferably glass, quartz, light-transmitting resin such as PMMA or polycarbonate resin, transparent metal deposition film, flexible film such as polydimethylsiloxane, photocured film, metal film, etc. The mold substrate is more preferably quartz because of its small thermal expansion coefficient and small pattern distortion.
[0168] The fine pattern on the surface of the mold preferably has a pattern height of 4 nm or more and 200 nm or less. A certain pattern height is necessary to increase the processing accuracy of the substrate, but the lower the pattern height, the lower the force required to peel the mold from the cured film in the process of separating the cured film and the mold described below, and the fewer defects remaining on the mask side after the resist pattern is torn off. Taking these factors into consideration, it is recommended to select and adopt a pattern height with an appropriate balance.
[0169] In addition, when the mold is peeled off, the elastic deformation of the resist pattern due to the impact can cause adjacent resist patterns to come into contact with each other, resulting in adhesion or damage to the resist patterns. This can sometimes be avoided by making the pattern height approximately twice the pattern width (aspect ratio 2 or less).
[0170] In order to improve the releasability between the curable composition and the surface of the mold, the mold may be subjected to a surface treatment in advance. As a method of surface treatment, a method of applying a release agent to the surface of the mold to form a release agent layer may be mentioned. As the release agent, a silicone-based release agent, a fluorine-based release agent, a hydrocarbon-based release agent, a polyethylene-based release agent, a polypropylene-based release agent, a paraffin-based release agent, a montan-based release agent, a carnauba-based release agent, etc. may be mentioned. Fluorine-based and hydrocarbon-based release agents are preferable. As a commercially available product, for example, Optool (registered trademark) DSX manufactured by Daikin Industries, Ltd. may be mentioned. The release agent may be used alone or in combination of two or more kinds.
[0171] In this step, the pressure applied to the curable composition when the mold and the curable composition are brought into contact with each other is not particularly limited. A pressure of 0 MPa or more and 100 MPa or less is recommended. The pressure is preferably 0 MPa or more and 50 MPa or less, 30 MPa or less, or 20 MPa or less.
[0172] If the pre-spreading of the droplets of the curable composition has progressed in the previous step (the step of applying the curable composition), the spreading of the curable composition in this step is completed quickly. As a result, the time for contacting the mold with the curable composition can be shortened. The contact time is not particularly limited, but is preferably 0.1 seconds or more and 600 seconds or less, 3 seconds or less, or 1 second or less. If the contact time is too short, the spreading and filling may be insufficient, and a defect called an unfilled defect may occur.
[0173] This step can be carried out under any of the conditions of air atmosphere, reduced pressure atmosphere, and inert gas atmosphere, but is preferably carried out under a pressure of 0.0001 atm or more and 10 atm or less. In order to prevent the influence of oxygen and moisture on the curing reaction, it is recommended to carry out the step under a reduced pressure atmosphere or in an inert gas atmosphere. Specific examples of inert gases that can be used to create an inert gas atmosphere include nitrogen, carbon dioxide, helium, argon, CFC, HCFC, HFC, and mixed gases thereof.
[0174] This step may be performed under an atmosphere containing a condensable gas (hereinafter referred to as a "condensable gas atmosphere"). In this specification, the condensable gas refers to a gas that is condensed and liquefied by the capillary pressure generated when the gas is filled into the recesses of the fine pattern formed on the mold and the gap between the mold and the substrate together with the curable composition. The condensable gas exists as a gas in the atmosphere before the curable composition comes into contact with the mold in this step. When this step is performed under a condensable gas atmosphere, the gas filled into the recesses of the fine pattern is liquefied by the capillary pressure generated by the curable composition, and the bubbles disappear, resulting in excellent filling properties. The condensable gas may be dissolved in the curable composition.
[0175] The boiling point of the condensable gas is not limited as long as it is equal to or lower than the atmospheric temperature in this step, but is preferably -10°C or higher, or +10°C or higher and +23°C or lower.
[0176] The vapor pressure of the condensable gas at the atmospheric temperature in this step is not particularly limited as long as it is equal to or lower than the mold pressure, and is preferably in the range of 0.1 MPa to 0.4 MPa.
[0177] Specific examples of condensable gases include chlorofluorocarbons (CFCs) such as trichlorofluoromethane, fluorocarbons (FCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs) such as 1,1,1,3,3-pentafluoropropane (CHF2CH2CF3, HFC-245fa, PFP), and hydrofluoroethers (HFEs) such as pentafluoroethyl methyl ether (CF3CF2OCH3, HFE-245mc).
[0178] The condensable gas may be used alone or in combination of two or more. The condensable gas may be used in combination with a non-condensable gas such as air, nitrogen, carbon dioxide, helium, argon, etc. Air and helium are preferred as non-condensable gases to be mixed with the condensable gas.
[0179] <Step of irradiating the curable composition film with light or electron beam to form a cured film> In this step, the curable composition film is irradiated with light or an electron beam to form a cured film. That is, the curable composition film filled in the fine pattern of the mold is irradiated with light or an electron beam through the mold, and the curable composition filled in the fine pattern of the mold is cured in that state to form a cured film having a pattern shape.
[0180] The light or electron beam is selected according to the sensitivity wavelength of the curable composition. Specifically, ultraviolet light, X-rays, electron beams, etc. having a wavelength of 150 nm or more and 400 nm or less can be appropriately selected and used. Examples of light or electron beam light sources include high pressure mercury lamps, ultra-high pressure mercury lamps, low pressure mercury lamps, Deep-UV lamps, carbon arc lamps, chemical lamps, metal halide lamps, xenon lamps, KrF excimer lasers, ArF excimer lasers, F2 excimer lasers, etc. The number of light sources may be one or more. Irradiation may be performed on the entire curable composition filled in the fine pattern of the mold, or only on a partial area. Light irradiation may be performed intermittently multiple times on the entire area on the substrate, or may be continuously irradiated on the entire area. In addition, a first irradiation may be performed on a partial area on the substrate, and a second irradiation may be performed on an area different from the partial area.
[0181] The cured film thus obtained preferably has a pattern with a size of 1 nm or more, or 10 nm or more, and 10 mm or less, or 100 μm or less.
[0182] <Step of separating the cured film from the mold> In this step, the cured film is separated from the mold. The patterned cured film is separated from the mold to obtain a free-standing cured film having a pattern that is a reverse pattern of the fine pattern formed on the mold.
[0183] The method for separating the cured film having a pattern shape from the mold is not particularly limited as long as it is a means for moving the cured film and the mold in a direction in which they are relatively separated from each other, as long as a part of the cured film having a pattern shape is not physically damaged, and various conditions are also not particularly limited. For example, the substrate may be fixed and the mold may be moved away from the substrate to be peeled off, or the mold may be fixed and the substrate may be moved away from the mold to be peeled off. Alternatively, the substrate and the mold may be pulled and moved in opposite directions to be peeled off.
[0184] In addition, when the above-mentioned step of contacting the curable composition with the mold is carried out in a condensable gas atmosphere, when the cured film is separated from the mold in this step, the pressure at the interface where the cured film and the mold are in contact with each other decreases, and the condensable gas evaporates, which makes it possible to reduce the release force required to separate the cured film from the mold.
[0185] By the above steps, a cured film having a desired concave-convex pattern shape derived from the concave-convex shape of the mold at desired positions can be prepared.
[0186] Although the pattern formation method using the imprint method has been described above, the resist underlayer film obtained from the composition for forming a resist underlayer film of the present invention is not limited to the pattern formation method using the imprint method, and can also be used, for example, as a resist underlayer film in a pattern formation method by a multilayer resist process.
[0187] [Method of manufacturing semiconductor device] A method for manufacturing a semiconductor device according to a first aspect of the present invention includes the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a resist film on the resist underlayer film; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; a step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film; processing the semiconductor substrate using the patterned underlayer film as a mask; Includes.
[0188] Further, a method for manufacturing a semiconductor device according to a second aspect of the present invention includes the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention; forming a hard mask on the resist underlayer film; further forming a resist film on the hard mask; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; Etching the hard mask using the formed resist pattern as a mask to obtain a patterned hard mask; Etching the underlayer film using the patterned hard mask as a mask to obtain a patterned resist underlayer film; processing the semiconductor substrate using the patterned resist underlayer film as a mask; Includes.
[0189] The first embodiment of the method for manufacturing a semiconductor device and the second embodiment of the method for manufacturing a semiconductor manufacturing apparatus will be described in detail below.
[0190] <First aspect> [Step of forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film of the present invention] In this step, for example, the resist underlayer film can be formed by the method for producing the resist underlayer film of the present invention described above.
[0191] [Step of forming a resist film on the resist underlayer film] Next, a step of forming a resist film on the resist underlayer film is performed.
[0192] The material of the resist film is not particularly limited as long as it is a resist material used in a multi-layer resist method.
[0193] [A process of forming a resist pattern by irradiating a resist film with light or an electron beam and then developing the resist film] Next, the resist film thus formed is irradiated with light or an electron beam, and then developed to form a resist pattern.
[0194] The light or electron beam to be irradiated can be appropriately selected depending on the properties of the resist film. The development method is not particularly limited as long as it is a method used in a multi-layer resist method.
[0195] [Step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film] Next, the resist underlayer film is etched using the previously formed resist pattern as a protective film.
[0196] In this step, the etching is preferably performed under conditions that allow the resist underlayer film to be etched more easily than the resist film. For example, when the resist film contains a large amount of silicon atoms, the resist film is difficult to remove by dry etching with an oxygen-based gas, and the resist underlayer film is preferentially etched. Therefore, dry etching with an oxygen-based gas is preferably performed.
[0197] This process makes it possible to obtain a patterned underlayer film.
[0198] [Processing the semiconductor substrate using the patterned underlayer film as a mask] Next, a process is carried out in which the semiconductor substrate is processed using the patterned underlayer film as a mask.
[0199] The semiconductor substrate is preferably processed by dry etching using a fluorine-based gas.
[0200] Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).
[0201] <Second aspect> The second embodiment differs from the first embodiment in that a hard mask is formed on the resist underlayer film, the hard mask is etched using the resist pattern as a mask, and the resist underlayer film is etched using the patterned hard mask. The second embodiment will be described below, focusing on the differences from the first embodiment.
[0202] The material of the hard mask is not particularly limited as long as it is a hard mask material that can be used in a multi-layer resist process.
[0203] For example, dry etching can be used for etching the inorganic hard mask. For example, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, chlorine trifluoride, chlorine, trichloroborane, dichloroborane, and other gases can be used for dry etching the inorganic hard mask. For example, halogen-based gases are used for dry etching the inorganic hard mask, and fluorine-based gases are more preferred. Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).
[0204] As in the second embodiment, in the present invention, after forming a resist underlayer film on a substrate, a hard mask is formed thereon, and a resist film is further coated thereon, thereby narrowing the pattern width of the resist film, and even if the resist film is thinly coated to prevent pattern collapse, the substrate can be processed by selecting an appropriate etching gas. For example, a fluorine-based gas that has a sufficiently high etching rate for the resist film can be used as an etching gas to process the resist underlayer film into a hard mask, a fluorine-based gas that has a sufficiently high etching rate for the hard mask can be used as an etching gas to process the resist underlayer film, and an oxygen-based gas that has a sufficiently high etching rate for the resist underlayer film can be used as an etching gas to process the substrate.
[0205] In both the first and second embodiments, an organic antireflective film can be formed on the resist underlayer film before the formation of a resist film or a hard mask. There is no particular limitation on the antireflective film composition used therein, and any composition commonly used in the lithography process can be selected and used, and the antireflective film can be formed by a commonly used method, such as coating with a spinner or coater and baking.
[0206] The resist underlayer film formed by the resist underlayer film forming composition of the present invention may also absorb light depending on the wavelength of the light used in the lithography process. In such a case, it can function as an anti-reflection film having the effect of preventing light reflected from the substrate. Furthermore, in the first embodiment, the underlayer film formed by the resist underlayer film forming composition of the present invention can also function as a hard mask. The underlayer film of the present invention can also be used as a layer for preventing the interaction between the substrate and the resist film, a layer having a function of preventing the adverse effect on the substrate of the material used in the resist film or the substance generated during exposure of the resist film, a layer having a function of preventing the diffusion of the substance generated from the substrate during heating and baking into the resist film, and a barrier layer for reducing the poisoning effect of the resist film due to the dielectric layer of the semiconductor substrate.
[0207] In addition, the underlayer film formed from the resist underlayer film forming composition of the present invention can be applied to a substrate having a via hole used in a dual damascene process, and can be used as a filling material capable of filling the hole without gaps. It can also be used as a planarizing material for planarizing the surface of a semiconductor substrate having irregularities.
[0208] As described above, the composition for forming a resist underlayer film of the present invention can realize a resist underlayer film that has excellent embedding properties and flatness and exhibits hardness sufficient to withstand processing. Therefore, the composition for forming a resist underlayer film of the present invention is also very useful in a method for manufacturing a semiconductor device including pattern formation by the multilayer resist method as described above. EXAMPLES
[0209] The present invention will be described in more detail below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. Note that the molecular weight was determined as the weight average molecular weight (Mw) in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.
[0210] [Synthesis examples and comparative synthesis examples] In each of the following synthesis examples and comparative synthesis examples, any of the aromatic compound group Ar1 (Ar1-1) to (Ar1-8), any of the polyetherification agent group (G1) to (G5), and any of the etherification agent group (R1-1) to (R1-8) shown below were used. Each raw material group is shown below.
[0211] [ka]
[0212] [ka]
[0213] [ka] (Ms represents a methanesulfonyl group)
[0214] [Synthesis Example 1] Synthesis of compound (A-1) for forming resist underlayer film 10.0g of aromatic compound (Ar1-1), 13.2g of polyetherification agent (G3), 16.7g of potassium carbonate, and 30g of N,N-dimethylformamide (DMF) were mixed, and the mixture was stirred at 120°C for 6 hours. Then, the temperature of the mixture was lowered to 90°C, and a solution of 4.6g of etherification agent (R1-1) and 10.0g of DMF was dropped into the mixture, and the mixture was stirred for another 16 hours. After the reaction, the mixture was returned to room temperature, dissolved in 150ml of methyl isobutyl ketone (MIBK), washed twice with 100ml of ultrapure water, further washed with 100ml of 3% aqueous nitric acid solution, and further washed four times with 100ml of ultrapure water. Next, the solvent was removed under reduced pressure, and 200g of propylene glycol monomethyl ether acetate (PGMEA) was added to the residue, and the solvent was removed again under reduced pressure to replace with PGMEA. As a result, a PGMEA solution of the compound (A-1) for forming a resist underlayer film, which is a polyether compound, was obtained.
[0215] (A-1): Mw = 2198 [ka]
[0216] [Synthesis Example 2] Synthesis of compound (A-2) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-2), which is a polyether compound, was obtained in the same manner as in Synthesis Example 1, except that the aromatic compound (Ar1-1) 10.0 g in Synthesis Example 1 was changed to 10.0 g of an aromatic compound (Ar1-2), the amount of polyetherification agent (G3) used was changed to 21.8 g, the amount of potassium carbonate used was changed to 27.6 g, and the amount of etherification agent (R1-1) used was changed to 7.5 g.
[0217] (A-2): Mw = 2439 [ka]
[0218] [Synthesis Example 3] Synthesis of compound (A-3) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-3), which is a polyether compound, was obtained in the same manner as in Synthesis Example 1, except that the aromatic compound (Ar1-1) 10.0 g in Synthesis Example 1 was changed to an aromatic compound (Ar1-3) 10.0 g, the amount of polyetherification agent (G3) used was changed to 13.6 g, the amount of potassium carbonate used was changed to 17.3 g, and the amount of etherification agent (R1-1) used was changed to 4.7 g.
[0219] (A-3): Mw = 2615 [ka]
[0220] [Synthesis Example 4] Synthesis of compound (A-4) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-4), which is a polyether compound, was obtained in the same manner as in Synthesis Example 1, except that the aromatic compound (Ar1-1) 10.0 g in Synthesis Example 1 was changed to an aromatic compound (Ar1-4) 10.0 g, the amount of polyetherification agent (G3) used was changed to 15.0 g, the amount of potassium carbonate used was changed to 19.0 g, and the amount of etherification agent (R1-1) used was changed to 5.2 g.
[0221] (A-4): Mw = 2320 [ka]
[0222] [Synthesis Example 5] Synthesis of compound (A-5) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-5), which is a polyether compound, was obtained in the same manner as in Synthesis Example 1, except that the aromatic compound (Ar1-1) (10.0 g) in Synthesis Example 1 was changed to the aromatic compound (Ar1-5) (10.0 g), the polyetherification agent (G3) was changed to the polyetherification agent (G1) (7.6 g), the amount of potassium carbonate used was changed to 20.0 g, the etherification agent (R1-1) was changed to the etherification agent (R1-2) (9.8 g), and the reaction temperature was changed to 60°C.
[0223] (A-5): Mw = 5594 [ka]
[0224] [Synthesis Example 6] Synthesis of compound (A-6) for forming resist underlayer film 10.0g of aromatic compound (Ar1-6), 7.9g of polyetherification agent (G3), 20.1g of potassium carbonate, and 30g of DMF were mixed, and the mixture was stirred at 120°C for 6 hours. Then, the mixture was cooled to 90°C, 3.5g of etherification agent (R1-3) was added, and the mixture was reacted for 6 hours. Then, the reaction mixture was cooled to 50°C, 8.9g of etherification agent (R1-2) was added, and the reaction was allowed to proceed for 16 hours. The reaction mixture was returned to room temperature, washed with 300ml of MIBK and 200ml of water, and washed with 150ml of 3% aqueous nitric acid solution. The reaction mixture was further washed four times with 200ml of water, and the solvent was removed under reduced pressure. Next, 300g of PGMEA was added to the residue, and the solvent was removed again under reduced pressure to replace the PGMEA. This resulted in a PGMEA solution of the resist underlayer film forming compound (A-6), which is a polyether compound.
[0225] (A-6): Mw = 6240 [ka]
[0226] [Synthesis Example 7] Synthesis of compound (A-7) for forming resist underlayer film 10.0g of aromatic compound (Ar1-7), 5.1g of polyetherification agent (G1), 17.9g of potassium carbonate, and 30g of DMF were mixed, and the mixture was stirred at 80°C for 6 hours. Then, the temperature of the mixture was increased to 90°C, 3.1g of etherification agent (R1-3) was added thereto, and the mixture was reacted for 6 hours. Then, the temperature of the reactant was increased to 50°C, 7.9g of etherification agent (R1-2) was added thereto, and the mixture was reacted for 16 hours. The reactant was returned to room temperature, washed with 300ml of MIBK and 200ml of water, and washed with 150ml of 3% aqueous nitric acid solution. Furthermore, the reactant was washed four times with 200ml of water, the solvent was removed under reduced pressure, 300g of PGMEA was added to the residue, and the solvent was removed again under reduced pressure to replace the PGMEA. As a result, a PGMEA solution of the resist underlayer film forming compound (A-7), which is a polyether compound, was obtained.
[0227] (A-7): Mw = 4425 [ka]
[0228] [Synthesis Example 8] Synthesis of compound (A-8) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-8), which is a polyether compound, was obtained in the same manner as in Synthesis Example 7, except that the polyetherification agent (G1) in Synthesis Example 7 was changed to 5.0 g of a polyetherification agent (G2), the etherification agent (R1-3) was changed to 3.5 g of an etherification agent (R1-4), and the etherification agent (R1-2) was changed to 6.4 g of an etherification agent (R1-5).
[0229] (A-8): Mw = 4400 [ka]
[0230] [Synthesis Example 9] Synthesis of compound (A-9) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-9), which is a polyether compound, was obtained in the same manner as in Synthesis Example 8, except that the etherification agent (R1-4) in Synthesis Example 8 was changed to 3.1 g of the etherification agent (R1-3) and the etherification agent (R1-5) was changed to 7.9 g of the etherification agent (R1-2).
[0231] (A-9): Mw=4515 [ka]
[0232] [Synthesis Example 10] Synthesis of compound (A-10) for forming resist underlayer film A PGMEA solution of a polyether compound, a compound for forming a resist underlayer film (A-10), was obtained in the same manner as in Synthesis Example 9, except that the etherification agent (R1-3) in Synthesis Example 9 was changed to 2.9 g of the etherification agent (R1-6).
[0233] (A-10): Mw = 4550 [ka]
[0234] [Synthesis Example 11] Synthesis of compound (A-11) for forming resist underlayer film 10.0g of aromatic compound (Ar1-7), 7.1g of polyetherification agent (G3), 17.9g of potassium carbonate, and 30g of DMF were mixed, and the mixture was stirred at 120°C for 6 hours. Then, the temperature of the mixture was set to 90°C, 3.1g of etherification agent (R1-3) was added thereto, and the mixture was reacted for 6 hours. Then, the temperature of the reactant was set to 50°C, 7.9g of etherification agent (R1-2) was added thereto, and the mixture was reacted for 16 hours. The reactant was returned to room temperature, washed with 300ml of MIBK and 200ml of water, and washed with 150ml of 3% aqueous nitric acid solution. Furthermore, the reactant was washed four times with 200ml of water, the solvent was removed under reduced pressure, 300g of PGMEA was added to the residue, and the solvent was removed again under reduced pressure to replace the PGMEA. As a result, a PGMEA solution of the resist underlayer film forming compound (A-11), which is a polyether compound, was obtained.
[0235] (A-11): Mw=4820 [ka]
[0236] [Synthesis Example 12] Synthesis of compound (A-12) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-12), which is a polyether compound, was obtained in the same manner as in Synthesis Example 11, except that the polyetherification agent (G3) in Synthesis Example 11 was changed to 9.0 g of the polyetherification agent (G4) and the etherification agent (R1-3) was changed to 3.9 g of the etherification agent (R1-8).
[0237] (A-12): Mw=4705 [ka]
[0238] [Synthesis Example 13] Synthesis of compound (A-13) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-13), which is a polyether compound, was obtained in the same manner as in Synthesis Example 11, except that the polyetherification agent (G1) in Synthesis Example 11 was changed to 8.3 g of the polyetherification agent (G5) and the etherification agent (R1-3) was changed to 3.4 g of the etherification agent (R1-7).
[0239] (A-13): Mw=4611 [ka]
[0240] [Synthesis Example 14] Synthesis of compound (A-14) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-14), which is a polyether compound, was obtained in the same manner as in Synthesis Example 1, except that the aromatic compound (Ar1-1) in Synthesis Example 1 was changed to 10.0 g of an aromatic compound (Ar1-8), the amount of the polyetherification agent (G3) used was changed to 6.5 g, the amount of potassium carbonate used was changed to 8.3 g, and the amount of the etherification agent (R1-2) used was changed to 2.0 g.
[0241] (A-14): Mw = 7100 [ka]
[0242] [Synthesis Example 15] Synthesis of compound (A-15) for forming resist underlayer film 5.0g of aromatic compounds (Ar1-2), 5.0g of (Ar1-7), 14.4g of polyetherification agent (G3), 22.7g of potassium carbonate, and 30g of N,N-dimethylformamide (DMF) were mixed, and the mixture was stirred at 120°C for 6 hours. After that, the temperature was raised to 90°C, 2.4g of etherification agent (R1-3) was added, and the mixture was reacted for 6 hours, and then the temperature was raised to 50°C, 4.9g of etherification agent (R1-2) was added, and the mixture was reacted for 16 hours. After the reaction, the mixture was returned to room temperature, dissolved in 150ml of methyl isobutyl ketone (MIBK), washed twice with 100ml of ultrapure water, further washed with 100ml of 3% aqueous nitric acid solution, and further washed four times with 100ml of ultrapure water. Next, the solvent was removed under reduced pressure, and 200g of propylene glycol monomethyl ether acetate (PGMEA) was added to the residue, and the solvent was removed again under reduced pressure to replace the PGMEA. As a result, a PGMEA solution of a compound for forming a resist underlayer film (A-15), which is a polyether compound, was obtained.
[0243] (A-15): Mw = 3230 [ka]
[0244] [Synthesis Example 16] Synthesis of compound (A-16) for forming resist underlayer film A PGMEA solution of a compound for forming a resist underlayer film (A-16), which is a polyether compound, was obtained in the same manner as in Synthesis Example 7, except that the amount of polyetherification agent (G1) used in Synthesis Example 7 was changed to 2.5 g and 3.5 g of polyetherification agent (G3) was further used.
[0245] (A-16): Mw=4344 [ka]
[0246] [Synthesis Example 17] Synthesis of compound (A-17) for forming resist underlayer film A PGMEA solution of a polyether compound (A-17) for forming a resist underlayer film was obtained in the same manner as in Synthesis Example 11, except that the amount of polyetherification agent (G3) used in Synthesis Example 11 was changed to 10.6 g.
[0247] (A-17): Mw = 13500 [ka]
[0248] [Comparative Synthesis Example 1] Synthesis of compound (R-1) for forming resist underlayer film 10.0g of 1,7-dihydroxynaphthalene, 4.8g of 37% aqueous formaldehyde solution, 0.3g of paratoluenesulfonic acid monohydrate, and 30g of PGME were mixed, and the mixture was stirred at 120°C for 20 hours. The resulting mixture was washed twice with 200ml of MIBK and 150ml of water. The solvent was removed from the mixture under reduced pressure, and then 200g of dimethylformamide was added to the residue, and the solvent was further removed under reduced pressure. Then, 19.0g of potassium carbonate and an additional 80g of DMF were added to the residue, and the mixture was stirred at 55°C, to which 20.4g of etherification agent (R1-2) was added dropwise, and the reaction was carried out for 20 hours. The reaction product was returned to room temperature, washed with 300ml of MIBK and 200ml of water, and washed with 150ml of 3% aqueous nitric acid solution. Furthermore, the reactant was washed four times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added to the residue, and the solvent was again removed under reduced pressure to replace with PGMEA, thereby obtaining a PGMEA solution of the resist underlayer film forming compound (R-1).
[0249] (R-1): Mw = 5324 [ka]
[0250] [Comparative Synthesis Example 2] Synthesis of compound (R-2) for forming resist underlayer film 10.0g of 1,5-dihydroxynaphthalene, 10.13g of 4-tert-butylbenzaldehyde, 50g of PGMEA, and 1.2g of methanesulfonic acid were mixed and reacted at 150°C for 2 hours. After the reaction was completed, the reaction solution was dropped into a mixed solution of methanol / water, reprecipitated, and the supernatant was decanted. 100g of PGMEA was added to the residue, and the solvent was replaced by drying under reduced pressure. This resulted in a PGMEA solution of the resist underlayer film forming compound (R-2).
[0251] (R-2): Mw = 4110 [ka]
[0252] [Comparative Synthesis Example 3] Synthesis of compound for forming resist underlayer film (R-3) 10.0 g of phenylnaphthylamine, 8.2 g of 9-fluorenone, 1.3 g of methanesulfonic acid, and 20 g of propylene glycol monomethyl ether acetate were mixed. The mixture was then heated to reflux under nitrogen and reacted for 14 hours. After the reaction was stopped, the reactant was reprecipitated with methanol, the upper layer was decanted, 100 g of PGMEA was added to the residue, and the mixture was dried under reduced pressure. This resulted in a PGMEA solution of the resist underlayer film forming compound (resin) (R-3).
[0253] (R-3): Mw = 1900 [ka]
[0254] [Preparation of composition for forming resist underlayer film UDL-1] Resin (A-1) was dissolved in propylene glycol monomethyl ether acetate (PGMEA) containing 0.5 mass % of surfactant FC-4430 (manufactured by Sumitomo 3M Limited) in the ratio shown in Table 1, and the resulting mixture was filtered through a 0.02 μm membrane filter to prepare a composition for forming a resist underlayer film (UDL-1).
[0255] [Preparation of compositions for forming resist underlayer films (UDL-2 to 24) and comparative compositions for forming resist underlayer films (Comparative UDL-1 to 3)] Except for the type and content of each component as shown in Table 1, the same procedure as for UDL-1 was used to prepare each chemical solution. In Table 1, "-" indicates that the corresponding component was not used. The comparative compound (R-4) was polyethylene glycol monomethyl ether acrylate (n = about 13) manufactured by Tokyo Kasei. The crosslinking agent used was the following formula (D-1), the thermally decomposable resin used was the following formula (E-1), the high boiling point solvent used was 1,6-diacetoxyhexane (B2-1): boiling point 260°C, and the thermal acid generator used was the following formula (TAG-1).
[0256] [Comparative Example Compound] The comparative compound (R-4) is shown below.
[0257] [ka]
[0258] [Crosslinking agent] The crosslinking agent (D-1) used in the composition for forming the resist underlayer film is shown below.
[0259] [ka]
[0260] [Example of synthesis of thermally decomposable resin] Synthesis of thermally decomposable resin (E-1) To a mixture of 3.8 g of a cation exchange resin (Amberlyst (registered trademark) 15) and 100 g of ethyl acetate, 100 g of diethylene glycol monovinyl ether was added at room temperature, and the mixture was further stirred for 3 hours. 0.8 g of triethylamine was added to the resulting mixture to stop the reaction, and the cation exchange resin was removed by filtration. The filtrate was concentrated under reduced pressure to obtain 100 g of a thermally decomposable resin polymer (E-1) as a highly viscous liquid.
[0261] The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, giving the following results: Mw=5,200, Mw / Mn=2.64.
[0262] [ka]
[0263] [Thermal acid generator] The thermal acid generator (TAG-1) used in the composition for forming the resist underlayer film is shown below. [ka]
[0264] [Table 1]
[0265] [Solvent resistance test] Each of the resist underlayer film forming compositions (UDL-1 to 26, Comparative Examples UDL-1 to 4) prepared above was applied onto a silicon substrate to obtain a coating film. The obtained coating film was baked at 180°C for 60 seconds, and then further baked at 350°C for 60 seconds. As a result, each resist underlayer film with a thickness of about 200 nm was formed.
[0266] The thickness (FT-1 [nm]) of the resist underlayer film formed was measured. Furthermore, OK73 thinner (propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate = 7 / 3) was dispensed on the resist underlayer film, then left for 30 seconds, then the resist underlayer film was spin-dried, and then the resist underlayer film was baked at 100 ° C for 60 seconds to evaporate the OK73 thinner (reworked). The thickness (FT-2 [nm]) of the resist underlayer film reworked in this way was measured.
[0267] The difference in film thickness before and after the treatment (film remaining rate: (FT-2 / FT-1) x 100) was determined. The results are shown in Table 2 below.
[0268] [Contact angle measurement / Hardness measurement] Each of the resist underlayer film forming compositions (UDL-1 to 26, Comparative Examples UDL-1 to 4) prepared above was applied onto a silicon substrate to obtain a coating film. Next, the coating film was baked at 180°C for 60 seconds, and then further baked at 350°C for 60 seconds. As a result, each resist underlayer film with a thickness of about 200 nm was formed.
[0269] The contact angle of these resist underlayer films with pure water was measured. In addition, a nanoindentation test was performed using a Nanoindenter SA2 type device manufactured by Toyo Corporation to measure the hardness of the resist underlayer films. The results are shown in Table 2.
[0270] [Table 2]
[0271] As shown in Table 2, the resist underlayer film forming composition of the present invention (Examples 1-1 to 1-26) all had a residual film ratio ((FT-2 / FT-1) x 100) before and after rework that exceeded 101%, suggesting that the film after baking was a porous film having a large number of pores into which the OK73 thinner could penetrate. In addition, among the examples using a polyether compound having a spiro ring structure in the mother nucleus, Examples 1-9 to 1-17 had a residual film ratio ((FT-2 / FT-1) x 100) of over 102%, suggesting that the porosity was increased by the two effects of the cyclic alkyl structure and cyclic alkyl ether of the mother nucleus. In addition, the residual film ratio ((FT-2 / FT-1) x 100) before and after rework of Examples 1-18 to 1-20, in which a crosslinking agent was added, was slightly suppressed compared to the corresponding examples of Examples 1-6, 1-9, and 1-11, in which no crosslinking agent was added. In addition, in Examples 1-21 to 1-23 in which a thermally decomposable resin was added, the residual film ratio ((FT-2 / FT-1) x 100) before and after rework was increased compared to the corresponding Examples 1-6, 1-9, and 1-11 in which no thermally decomposable resin was added. This shows that the porosity can be adjusted by adding a crosslinking agent and a thermally decomposable resin.
[0272] No improvement in the residual film rate was confirmed in Comparative Example 1-1, which is a novolak resin in which an ether substituent was introduced using a similar mother nucleus, or in Comparative Example 1-2, which is a novolak resin in which the hydroxyl group was left as it was. This result suggests that the polyether structure is important for making the film porous.
[0273] In Comparative Example 1-3, the residual film rate was 99.9%, which was extremely low.
[0274] Furthermore, in Comparative Example 1-4, in which a polyether compound not containing an aromatic ring was used, sublimation was so severe that various measurements could not be performed. This confirmed that the introduction of an aromatic ring is effective not only for improving processing resistance but also for suppressing sublimate formation.
[0275] In addition, when comparing the contact angle of Example 1-1 in which fluorine was introduced and that of Example 1-2 in which fluorine was not introduced, the difference was about 10 degrees, confirming the possibility that they can be used separately depending on the hydrophilicity or hydrophobicity of the gas species used.
[0276] Furthermore, in Examples 1-1 to 1-26, the hardness measured as an index of processing resistance exceeded 0.55 GPa, and some even exceeded 0.7 GPa, confirming that the samples had sufficient processing resistance.
[0277] [Evaluation of embedding characteristics] The resist underlayer film forming compositions (UDL-1 to 26, Comparative Examples UDL-2 to 3) prepared above were each applied onto a SiO2 wafer substrate having a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, distance between the centers of two adjacent holes 0.32 μm), and the applied film was baked at 180° C. for 60 seconds, and then further baked at 350° C. for 60 seconds. As a result, each resist underlayer film with a thickness of 200 nm was formed on the substrate having the dense hole pattern.
[0278] The cross-sectional shape of each of the obtained wafer substrates was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd., to confirm whether the holes were filled with an organic film without any voids (air gaps). The results are shown in Table 3 below. When a composition for forming a resist underlayer film with poor filling properties was used, voids were generated inside the holes. When a composition for forming a resist underlayer film with good filling properties was used, the organic film was filled without any voids in this evaluation. The evaluation was as follows: A: Filling possible without voids, B: Microvoids present, C: Voids present or filling not possible.
[0279] [Table 3]
[0280] As shown in Table 3, in Examples 2-1 to 2-26 using the resist underlayer film forming compositions (UDL-1 to 26) of the present invention, it was possible to fill a dense hole pattern without generating voids, except for Example 2-17, and it was confirmed that good filling characteristics were achieved. Example 2-17, in which voids were observed, used a polymer with a molecular weight of 13,500, and it is believed that the molecular weight was too large to fill the bottom well, which is why the voids were observed. Moreover, no voids were observed in compositions to which a crosslinking agent or a thermally decomposable resin was added.
[0281] In Comparative Example 2-1, in which Comparative Example UDL-2 was used, the result was that embedding was not possible. This is thought to be because the compound R-2 of Comparative Example UDL-2 does not have an ether substituent and remains a rigid resin structure, resulting in low resin fluidity and making it impossible to embed the resin in the fine pattern.
[0282] In addition, for Comparative Example 2-2, which used Comparative Example UDL-3, a larger void was confirmed in the bottom than in Example 2-17. This is thought to be because the resin of Comparative Example UDL-3 does not have crosslinking properties itself, and a large amount of crosslinking agent and thermal acid generator was added, which resulted in decomposition of the resin and additives and a large amount of sublimation.
[0283] [Flattening characteristics evaluation] Each of the resist underlayer film forming compositions prepared above was applied onto a SiO2 wafer substrate having a giant isolated trench pattern (trench width 10 μm, trench depth 0.1 μm), and the resulting coating film was baked at 180 ° C for 60 seconds, and then further baked at 350 ° C for 60 seconds. In this way, each resist underlayer film was formed on a substrate having a giant isolated trench pattern. The step between the trench portion and the non-trench portion of the resist underlayer film was observed using an atomic force microscope (AFM) NX10 manufactured by Park Systems. The results are shown in Table 4. In this evaluation, the smaller the step, the better the planarization characteristics. In this evaluation, a trench pattern with a depth of 0.10 μm was planarized using an organic film forming composition with a normal film thickness of about 0.2 μm, and the evaluation conditions were strict to evaluate the superiority or inferiority of the planarization characteristics. [Table 4]
[0284] As shown in Table 4, it was confirmed that Examples 3-1 to 3-5 using each of the resist underlayer film forming compositions (UDL-6, 9, 11, 15 and 16) of the present invention were significantly superior in flatness compared to Comparative Example 3-3, which has a significantly different resin structure. In addition, it was confirmed that the step between the patterned part and the non-patterned part of the film was small and the flattening characteristics were excellent compared to Comparative Examples 3-1 and 3-2, in which a novolak resin was prepared using a similar mother nucleus. In addition, Examples 3-4 to 3-5 using multiple Ar1 structures and R1 structures (UDL-15 and 16) showed improved flatness. This is considered to be the result of promoting fluidity by combining the two. When comparing Examples 3-6 to 11 and Example 3-14, in which a crosslinking agent (D-1) or a thermally decomposable resin (E-1) was added, with Examples 3-1 to 3-3, in which no crosslinking agent was added, there was no significant change in flatness, and it is considered that the addition of a crosslinking agent or a thermally decomposable resin that can adjust the porosity of the film does not affect the flatness. In addition, in Examples 3-12 to 3-13 in which the high boiling point solvent (B2-1) was added, the flatness was improved compared to Examples 3-2 and 3-3 in which the high boiling point solvent was not added. This is believed to be due to the improvement in thermal fluidity caused by the high boiling point solvent.
[0285] From the above, the composition for forming a resist underlayer film of the present invention exhibits high filling and planarization properties that can be used as an underlayer film, has high hardness and excellent processing resistance, and can form a porous and low-density film, so that it can provide a resist underlayer film that is also excellent in gas permeability. Such a resist underlayer film is particularly useful for nanoimprinting and is also suitable for use in a multilayer resist process.
[0286] The present specification includes the following aspects. [1] A composition for forming a resist underlayer film, comprising: (A) a polyether compound having a repeating unit represented by the following general formula (I); and (B) an organic solvent: [ka] (In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected to an aliphatic ring or a heterocycle, or a linear, branched or cyclic hydrocarbon group, or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via an ether group or a carbonyl group; Ar1 may be one type or a combination of multiple types in the same resin; R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, R2 is any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom, and R3 may be one or more types in the same resin and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. n and m are integers of 0 or more. [2] In the above general formula (I), at least one of the R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and wherein the structure R II-1 The composition for forming a resist underlayer film according to [1], wherein a satisfies 1≦a≦100, where a is the ratio of [ka] (In formula (II-1), * represents a bond to an oxygen atom.) [3] In the above general formula (I), R3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2and II-1 The ratio of the structure R II-2 The composition for forming a resist underlayer film according to [1], wherein when the ratio of a to b is taken as the ratio of a to b, the relationships of 1≦a≦99, 1≦b≦99, and a+b=100 are satisfied. [ka] (In formula (II-1) and formula (II-2), * represents a bond to an oxygen atom.) [4] The composition for forming a resist underlayer film according to any one of [1] to [3], characterized in that in the above general formula (I), R1 is selected from the group consisting of groups represented by the following general formulas (III-1) to (III-3). [ka] (In formulas (III-1) to (III-3), * represents a bond to an oxygen atom.) [5] The composition for forming a resist underlayer film according to any one of [1] to [4], wherein, in the above general formula (I), Ar1 is selected from the group consisting of structures represented by the following formula (Ar-1): [ka] (In formula (Ar-1), * represents a bond to the oxygen atom of -O-R1- or OR3.) [6] The composition for forming a resist underlayer film according to any one of [1] to [5], wherein the polyether compound has a weight average molecular weight Mw of 2,000 to 12,000 in terms of polystyrene, as determined by a gel permeation chromatography method. [7] The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180°C for 60 seconds, and then additionally baked at 350°C for 60 seconds. The thickness of the coating film after the additional baking is designated as FT-1. After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is dispensed onto the coating film, which is then left for 30 seconds. The coating film is then spin-dried, and then baked at 100°C for 60 seconds to evaporate the OK73 thinner. The thickness of the coating film after the additional baking is designated as FT-2. 101<{(FT-2) / (FT-1)}×100 The composition for forming a resist underlayer film according to any one of [1] to [6], wherein [8] The composition for forming a resist underlayer film according to any one of [1] to [7], further comprising (C) a surfactant. [9] (D) A composition for forming a resist underlayer film further comprising a crosslinking agent, the composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180°C for 60 seconds, and then additionally baked at 350°C for 60 seconds. The thickness of the coating film after the additional baking is designated as FT-1. After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is dispensed onto the coating film, and the coating film is left to stand for 30 seconds. The coating film is then spin-dried, and then baked at 100°C for 60 seconds to evaporate the OK73 thinner. The thickness of the coating film after the additional baking is designated as FT-2. 100<{(FT-2) / (FT-1)}×100<103 The composition for forming a resist underlayer film according to any one of [1] to [6], wherein
[10] (E) A resist underlayer film forming composition further comprising a thermally decomposable resin, the composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180°C for 60 seconds, and then additionally baked at 350°C for 60 seconds. The thickness of the coating film after the additional baking is designated as FT-1. After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is dispensed onto the coating film, and the coating film is left to stand for 30 seconds. The coating film is then spin-dried, and then baked at 100°C for 60 seconds to evaporate the OK73 thinner. The thickness of the coating film after the additional baking is designated as FT-2. 101.5<{(FT-2) / (FT-1)}×100 The composition for forming a resist underlayer film according to any one of [1] to [6], wherein
[11] A resist underlayer film forming composition further comprising both (D) a crosslinking agent and (E) a thermally decomposable resin, the composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180°C for 60 seconds, and then additionally baked at 350°C for 60 seconds. The thickness of the coating film after the additional baking is designated as FT-1. After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is dispensed onto the coating film, and the coating film is left to stand for 30 seconds. The coating film is then spin-dried, and then baked at 100°C for 60 seconds to evaporate the OK73 thinner. The thickness of the coating film after the additional baking is designated as FT-2. 100<{(FT-2) / (FT-1)}×100 The composition for forming a resist underlayer film according to any one of [1] to [6], wherein
[12] (F) The composition for forming a resist underlayer film according to any one of [1] to
[11] , further comprising an acid generator.
[13] The composition for forming a resist underlayer film according to any one of [1] to
[12] , wherein the composition for forming a resist underlayer film is for nanoimprinting.
[14] A resist underlayer film, which is a cured product of a coating film made of the composition for forming a resist underlayer film according to any one of [1] to
[12] .
[15] A method for producing a resist underlayer film, comprising: applying the composition for forming a resist underlayer film according to any one of [1] to
[12] onto a semiconductor substrate to obtain a coating film; and baking the coating film to obtain a resist underlayer film.
[16] A pattern formation method, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from a resist underlayer film-forming composition according to any one of [1] to
[12] ; forming a curable composition film on the resist underlayer film; contacting the curable composition film with a mold; irradiating the curable composition film with light or an electron beam to form a cured film; and separating the cured film from the mold.
[17] The pattern formation method according to
[16] , wherein the step of forming a curable composition film on the resist underlayer film comprises forming an adhesion layer and / or a silicone layer containing 99 mass % or less of Si on the resist underlayer film by coating or vapor deposition, and then forming a curable composition film thereon.
[18] A method for manufacturing a semiconductor device, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film according to any one of [1] to
[12] ; forming a resist film on the resist underlayer film; irradiating the resist film with light or an electron beam and then developing it to form a resist pattern; etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film; and processing the semiconductor substrate using the patterned underlayer film as a mask.
[19] A method for manufacturing a semiconductor device, comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film according to any one of [1] to
[12] ; forming a hard mask on the resist underlayer film; further forming a resist film on the hard mask; irradiating the resist film with light or an electron beam, followed by development, to form a resist pattern; etching the hard mask using the formed resist pattern as a mask to obtain a patterned hard mask; etching the underlayer film using the patterned hard mask as a mask to obtain a patterned resist underlayer film; and processing the semiconductor substrate using the patterned resist underlayer film as a mask.
[0287] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. (A) a polyether compound containing a repeating unit represented by the following general formula (I), (B) an organic solvent; A composition for forming a resist underlayer film, comprising: 【Chemistry 1】 (In the above general formula (I), Ar 1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms condensed or connected to an aliphatic ring or a heterocycle, or a plurality of substituted or unsubstituted aryl groups having 6 to 30 carbon atoms connected to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group; 1 may be one type or a combination of multiple types in the same resin, R 1 is a substituted or unsubstituted linear, branched or cyclic, saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic heteroalkylene group having 1 to 20 carbon atoms; R 2 is any one of a substituted or unsubstituted linear, branched or cyclic, saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, and a halogen atom; R 3 may be one type or a combination of multiple types in the same resin, and is a hydrogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted linear, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic alkynyl group having 2 to 20 carbon atoms. n and m are integers of 0 or more.)
2. In the general formula (I), the R 3 At least one of the structures R is selected from the group consisting of groups represented by the following formula (II-1): II-1 and the structure R II-1 2. The composition for forming a resist underlayer film according to claim 1, wherein a satisfies 1≦a≦100, where a is a ratio of 【Chemistry 2】 (In formula (II-1), * represents a bond to an oxygen atom.)
3. In the above general formula (I), R 3 is a structure R selected from the group consisting of groups represented by the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 and II-1 The ratio of the structure R II-2 2. The composition for forming a resist underlayer film according to claim 1, wherein, when a ratio of said compound is b, the relationships 1≦a≦99, 1≦b≦99, and a+b=100 are satisfied. 【Chemistry 3】 (In formula (II-1) and formula (II-2), * represents a bond to an oxygen atom.)
4. In the above general formula (I), R 1 is selected from the group consisting of groups represented by the following general formulas (III-1) to (III-3): 【Chemistry 4】 (In formulas (III-1) to (III-3), * represents a bond to an oxygen atom.)
5. In the above general formula (I), Ar 1 is selected from the group consisting of structures represented by the following formula (Ar-1): 【Chemistry 5】 (In formula (Ar-1), * represents -O-R 1 -OR 3 It represents the bond with the oxygen atom of
6. 2. The composition for forming a resist underlayer film according to claim 1, wherein the polyether compound has a weight average molecular weight Mw of 2,000 to 12,000 in terms of polystyrene as determined by gel permeation chromatography.
7. The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1, After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, which was then left for 30 seconds, spin-dried, and baked at 100° C. for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film was FT-2, 101<{(FT-2) / (FT-1)}×100 2. The composition for forming a resist underlayer film according to claim 1,
8. The composition for forming a resist underlayer film according to claim 1 , further comprising (C) a surfactant.
9. (D) further comprising a crosslinking agent; The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1, After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, which was then left for 30 seconds, spin-dried, and baked at 100° C. for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film was FT-2, 100<{(FT-2) / (FT-1)}×100<103 2. The composition for forming a resist underlayer film according to claim 1,
10. (E) further comprising a thermally decomposable resin; The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1, After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, which was then left for 30 seconds, spin-dried, and baked at 100° C. for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film was FT-2, 101.5<{(FT-2) / (FT-1)}×100 2. The composition for forming a resist underlayer film according to claim 1,
11. Further comprising both (D) a crosslinking agent and (E) a thermally decomposable resin; The composition for forming a resist underlayer film is applied to a substrate to obtain a coating film, the coating film is baked at 180° C. for 60 seconds, and then additionally baked at 350° C. for 60 seconds. The thickness of the coating film after the baking is designated as FT-1, After the additional baking, OK73 thinner obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 was dispensed onto the coating film, which was then left for 30 seconds, spin-dried, and baked at 100° C. for 60 seconds to evaporate the OK73 thinner. When the thickness of the coating film was FT-2, 100<{(FT-2) / (FT-1)}×100 2. The composition for forming a resist underlayer film according to claim 1,
12. 2. The composition for forming a resist underlayer film according to claim 1, further comprising (F) an acid generator.
13. The composition for forming a resist underlayer film according to any one of claims 1 to 12, wherein the composition for forming a resist underlayer film is for nanoimprinting.
14. A resist underlayer film, which is a cured product of a coating film comprising the composition for forming a resist underlayer film according to any one of claims 1 to 12.
15. Coating a composition for forming a resist underlayer film according to any one of claims 1 to 12 on a semiconductor substrate to obtain a coating film; baking the coating film to obtain a resist underlayer film. A method for producing a resist underlayer film, comprising:
16. A pattern formation method comprising the steps of: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film according to any one of claims 1 to 12; forming a curable composition film on the resist underlayer film; contacting the curable composition film with a mold; a step of irradiating the curable composition film with light or an electron beam to form a cured film; separating the cured film from the mold; A pattern forming method comprising the steps of:
17. The pattern forming method according to claim 16, wherein the step of forming a curable composition film on the resist underlayer film comprises forming an adhesion layer and / or a silicone layer containing 99% by mass or less of Si on the resist underlayer film by coating or vapor deposition, and forming a curable composition film thereon.
18. A method for manufacturing a semiconductor device, comprising: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film according to any one of claims 1 to 12; forming a resist film on the resist underlayer film; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; a step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film; processing the semiconductor substrate using the patterned underlayer film as a mask; 2. A method for manufacturing a semiconductor device comprising the steps of:
19. A method for manufacturing a semiconductor device, comprising: forming a resist underlayer film on a semiconductor substrate from the composition for forming a resist underlayer film according to any one of claims 1 to 12; forming a hard mask on the resist underlayer film; further forming a resist film on the hard mask; a step of irradiating the resist film with light or an electron beam, and then developing the resist film to form a resist pattern; Etching the hard mask using the formed resist pattern as a mask to obtain a patterned hard mask; Etching the underlayer film using the patterned hard mask as a mask to obtain a patterned resist underlayer film; processing the semiconductor substrate using the patterned resist underlayer film as a mask; 2. A method for manufacturing a semiconductor device comprising the steps of:
Citation Information
Patent Citations
Method for forming graded structures using imprint lithography
JP2006524919A
Lower layer film composition for imprinting, and pattern forming method using the same
JP2013202982A
Polymerizable compound for forming a template, curable composition thereof, and cured product thereof
JP6703253B2
Composition for forming resist underlayer film for nanoimprinting
WO2021125036A1
Resist underlayer film forming composition for nanoimprinting
WO2023145923A1
Cited By
JPWO2026074762A1
Naphthylene ether resin, resin composition, cured article, prepreg, circuit board, build-up film, semiconductor sealing material, semiconductor device, method for producing naphthylene ether resin, and method for producing phenolic resin
WO2026074762A1